Method for producing sulfide solid electrolyte, sulfide solid electrolyte, all-solid-state battery, and method for selecting raw material compounds used in producing sulfide solid electrolyte
By using specific raw material compounds with controlled defective energy, the method addresses N discharge and thermal instability issues in sulfide solid electrolytes, resulting in improved air and thermal stability for all-solid batteries.
Patent Information
- Application Number
- JP2024192551
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-06-03
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methods for manufacturing sulfide solid electrolytes face issues such as the discharge of nitrogen (N) outside the system and insufficient thermal stability, leading to reduced performance and limited operating temperatures of batteries.
A method involving the use of specific raw material compounds containing P, S, N, element A, and element M, where A is selected from Li, Na, K, and M is selected from Al, Ta, Si, Sc, Mg, Mg, Nb, B, HF, C, P, Zr, and Ti, to suppress N discharge and enhance thermal stability by controlling the defective energy of N through first-principle calculations.
The method effectively suppresses N discharge during manufacturing, improving air and thermal stability of sulfide solid electrolytes, thereby enhancing the performance and operating temperature range of all-solid batteries.
Smart Images

Figure 2025016664000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a sulfide solid electrolyte, a sulfide solid electrolyte, an all-solid-state battery, and a method for selecting raw material compounds used in the production of a sulfide solid electrolyte.
[0002] Due to their high energy density, non-aqueous electrolyte secondary batteries, such as lithium ion non-aqueous electrolyte secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc. The non-aqueous electrolyte secondary batteries generally include an electrode assembly having a pair of electrically isolated electrodes, and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes.
[0003] In recent years, sulfide solid electrolytes have been attracting attention as non-aqueous electrolytes for non-aqueous electrolyte secondary batteries, and various studies have been conducted on them.
[0004] In Patent Document 1, Li 2 S, P 2 S 5 , and Li 3 Starting from N, 75Li 2 S-25P 2 S 5 -yLi 3 It is described that a sulfide solid electrolyte having a composition of N is produced. In Patent Document 2, Li 2 S, P 2 S 5 , LiBr, LiI, and Li 3 It is described that a sulfide solid electrolyte is produced by using a raw material composition consisting of N. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2018-041671 [Patent Document 2] Patent Publication No. 2015-011898 [Patent Document 3] Patent Publication No. 2018-156735 Summary of the Invention [Problem to be solved by the invention]
[0006] Patent Document 1 describes that the atmospheric stability (water resistance) of the sulfide solid electrolyte can be improved by including N in the sulfide solid electrolyte. However, Li 3 When N was used, there was a problem of N being discharged outside the system.
[0007] In Patent Document 2, Li 2 S, P 2 S 5 It is described that a high Li ion conductive phase is precipitated by amorphizing a raw material composition containing Li, LiI, and LiBr and then heat-treating it. However, there is a problem that a low Li ion conductive phase is precipitated if the heat treatment temperature is too high. In Patent Document 3, Li 3 Although it has been reported that the addition of N can increase the difference in temperature between the formation of a high Li-ion conductive phase and the formation of a low Li-ion conductive phase, the difference is small, at a maximum of about 30°C, and further improvement is required.
[0008] The present invention has been made in view of the above-mentioned circumstances, and an object of one aspect of the present invention is to provide a method for producing a sulfide solid electrolyte that can suppress the emission of N to the outside of the system in the production process of the sulfide solid electrolyte, a method for selecting raw material compounds used in the production of the sulfide solid electrolyte, and an all-solid-state battery including the sulfide solid electrolyte. Another object of the present invention is to provide a sulfide solid electrolyte having improved thermal stability, a method for producing the same, and an all-solid-state battery including the sulfide solid electrolyte. [Means for solving the problem]
[0009] One aspect of the present invention made to solve the above problems is a method for producing a sulfide solid electrolyte, comprising: preparing a composition containing P, S, N, element A, and element M; reacting the composition to obtain an intermediate; and heating the intermediate to obtain a sulfide solid electrolyte, the composition including a raw material compound containing N, element A, and element M. A represents at least one element selected from the group consisting of Li, Na, and K. M represents at least one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, P, Zr, and Ti.
[0010] Another aspect of the present invention is a method for selecting raw material compounds used in the production of a sulfide solid electrolyte, comprising the steps of: As a candidate for the raw material compound, a candidate material containing N, element A', and element M' is selected, and the defect formation energy E of N in the inside of the candidate material is calculated by using first-principles calculation. Ndefect and calculating E Ndefect is 4.00 eV or more, the candidate material is selected as the raw material compound.
[0011] Another aspect of the present invention is a sulfide solid electrolyte having a crystal structure and containing, as constituent elements, P, S, N, element A, element X, and element M. Here, A represents at least one element selected from the group consisting of Li, Na, and K. X represents at least one element selected from the group consisting of Cl, Br, and I. M represents at least one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, P, Zr, and Ti. Effect of the Invention
[0012] According to the method for producing a sulfide solid electrolyte, the method for selecting raw material compounds used in the production of a sulfide solid electrolyte, and the sulfide solid electrolyte of one embodiment of the present invention, it is possible to suppress the emission of N to the outside of the system in the production process of the sulfide solid electrolyte. According to the sulfide solid electrolyte of another aspect of the present invention, it is possible to obtain a sulfide solid electrolyte having improved thermal stability. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a flow chart of a process for producing a sulfide solid electrolyte in one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an all-solid-state battery according to one embodiment of the present invention. [Diagram 3] FIG. 3 is an XRD diffraction pattern of the sulfide solid electrolyte of the example. [Figure 4] FIG. 4 is an XRD diffraction pattern of a sulfide solid electrolyte of a comparative example. [Diagram 5] FIG. 5 shows DSC curves of intermediates of the sulfide solid electrolytes of the examples and comparative examples after milling treatment and before heat treatment. [Figure 6] FIG. 6 shows DSC curves of intermediates of the sulfide solid electrolytes of the examples and comparative examples after milling and before heat treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] First, an overview of the method for producing a sulfide solid electrolyte disclosed in this specification will be described.
[0015] A method for producing a sulfide solid electrolyte according to one embodiment of the present invention includes preparing a composition containing P, S, N, element A, and element M, reacting the composition to obtain an intermediate, and heating the intermediate to obtain a sulfide solid electrolyte, the composition including a raw material compound containing N, element A, and element M. Here, A represents at least one element selected from the group consisting of Li, Na, and K. M represents at least one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, P, Zr, and Ti.
[0016] In the present invention, the term "composition" refers to a mixture of two or more compounds. The term "raw material compound" refers to a specific compound that constitutes the composition.
[0017] The inventors have found that by using a raw material compound containing at least one element A selected from the group consisting of Li, Na, and K, at least one element M selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, P, Zr, and Ti, and N, it is possible to suppress the emission of N to the outside of the system in a production process of a sulfide solid electrolyte, and have arrived at the present invention.
[0018] According to the method for producing a sulfide solid electrolyte, it is possible to suppress the emission of N to the outside of the system during the production process of the sulfide solid electrolyte. This makes it easier to control the content of N in the sulfide solid electrolyte. Although the reason for this is unclear, the following reason is presumed. Li disclosed in Patent Document 1 and Patent Document 3 3 In the method for producing a sulfide solid electrolyte using N, Li 3 The defect formation energy of N is small, and N 2 Gas is easily produced. In contrast, in the method for producing the sulfide solid electrolyte using a raw material compound containing N, element A, and element M, the defect formation energy of N is large, and N defects are unlikely to be formed during the synthesis of the sulfide solid electrolyte. 2 Gas is less likely to be generated, which makes it possible to suppress the emission of N outside the system during the production process of sulfide solid electrolytes. The element M is calculated by the first-principles calculation described later. α M β In a compound represented by N (α and β are values that give a stoichiometric ratio according to the type of element M), the defect formation energy of N is 4.00 eV or more. The defect formation energy of N will be defined later.
[0019] The raw material compound containing N, the element A, and the element M preferably contains Li, N, the element A, and the element M.
[0020] This makes it possible to increase the mass energy density of an all-solid-state battery including a sulfide solid electrolyte produced by this production method, since Li has the smallest atomic weight and smallest ion size among alkali metal elements.
[0021] The raw material compound containing N, element A, and element M may be obtained by reacting a nitride of element M with a nitride of element A, or may be an industrially produced and commercially available compound.
[0022] The element M is preferably one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, and P. These elements are elements for which the N defect formation energy calculated by the first-principles calculation described later is 4.10 eV or more.
[0023] This makes it possible to more reliably suppress the emission of N to the outside of the system during the production process of the sulfide solid electrolyte.
[0024] The element M is more preferably at least one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, and B. These elements are elements whose N defect formation energy calculated by the first-principles calculation described later is 4.35 eV or more.
[0025] This makes it possible to more reliably suppress the emission of N to the outside of the system during the production process of the sulfide solid electrolyte.
[0026] The composition preferably contains lithium sulfide, phosphorus sulfide, and raw material compounds containing N, element A, and element M. These compounds are easy to handle, and therefore can improve the productivity of the sulfide solid electrolyte.
[0027] In the composition, the element A preferably contains Li, the molar ratio of Li to P in the composition is 2.30 to 4.20, and the molar ratio of N to P in the composition is 0.0100 to 1.20. It is more preferable that the element A contains Li, the molar ratio of Li to P in the composition is 2.77 to 3.38, and the molar ratio of N to P in the composition is 0.280 to 0.650. This makes it possible to provide a sulfide solid electrolyte that is excellent in atmospheric stability and has high ionic conductivity at 25°C.
[0028] The composition preferably contains an element X. X is at least one element selected from the group consisting of Cl, Br, and I.
[0029] It is known that a sulfide solid electrolyte containing Li, P, S, and an element X generates a metastable phase with high ionic conductivity (hereinafter also referred to as HICP (High Ion Conduction Phase)) (Patent Document 2). It is also known that when such a sulfide solid electrolyte contains N, the difference between the heat treatment temperature at which HICP precipitates and the heat treatment temperature at which HICP undergoes a phase transition to another phase with low ionic conductivity (hereinafter also referred to as LICP (Low Ion Conduction Phase)) is widened (Patent Document 3). However, since the sulfide solid electrolyte is produced using Li3N in Patent Document 3, N is discharged outside the system during the production process of the sulfide solid electrolyte, and the effect of widening the heat treatment temperature range in which HICP is stable is not sufficiently obtained. In contrast, the method for producing a sulfide solid electrolyte suppresses the emission of N to the outside of the system, and therefore the effect of improving the thermal stability of the HICP can be fully exerted.
[0030] The composition preferably has a molar ratio of Li to P of 3.10 or more and 4.20 or less, a molar ratio of N to P of 0.0600 or more and 0.750 or less, and a molar ratio of X to P of 0.180 or more and 1.30 or less.
[0031] This makes it possible to provide a sulfide solid electrolyte having high thermal stability of HICP.
[0032] A sulfide solid electrolyte according to another aspect of the present invention is a sulfide solid electrolyte produced by the method for producing a sulfide solid electrolyte. With such a sulfide solid electrolyte, the emission of N to the outside of the system during the production process of the sulfide solid electrolyte is suppressed, and therefore various effects due to the inclusion of N can be fully exhibited.
[0033] An all-solid-state battery according to another aspect of the present invention includes a sulfide solid electrolyte produced by the method for producing a sulfide solid electrolyte. In such an all-solid-state battery, N is prevented from being discharged outside the system during the production process of the sulfide solid electrolyte, and therefore various effects due to the inclusion of N can be fully exhibited.
[0034] A method for selecting a raw material compound used in the production of a sulfide solid electrolyte according to another embodiment of the present invention is a method for selecting a raw material compound used in the production of a sulfide solid electrolyte, comprising the steps of: selecting a candidate material containing N, an element A', and an element M' as a candidate for the raw material compound; and calculating a defect formation energy E of N in the candidate material using first-principles calculations. Ndefect and calculating E Ndefect is 4.00 eV or more, the candidate material is selected as the raw material compound. In addition, if there are multiple N occupied sites in the crystal structure of the candidate material, E Ndefect The lowest value is the E of the candidate material. Ndefect Used as.
[0035] The raw material compounds selected by this selection method have a large N defect formation energy, and N defects are unlikely to form during the synthesis of sulfide solid electrolytes. 2Therefore, when the sulfide solid electrolyte is produced using the above-mentioned raw material compounds, it is possible to suppress the emission of N to the outside of the system during the production process of the sulfide solid electrolyte.
[0036] Above E Ndefect is 4.10 eV or more, the candidate material is preferably selected as the raw material compound.
[0037] This makes it possible to more reliably suppress the emission of N to the outside of the system during the production process of the sulfide solid electrolyte.
[0038] Above E Ndefect is 4.35 eV or more, it is more preferable to select the candidate material as the raw material compound.
[0039] This makes it possible to more reliably suppress the emission of N to the outside of the system during the production process of the sulfide solid electrolyte.
[0040] A method for producing a sulfide solid electrolyte according to another aspect of the present invention includes preparing a composition containing raw material compounds selected by a method for selecting raw material compounds to be used in the production of the sulfide solid electrolyte, reacting the composition to obtain an intermediate, and heating the intermediate to obtain the sulfide solid electrolyte.
[0041] This makes it possible to suppress the emission of N to the outside of the system during the production process of the sulfide solid electrolyte, making it easier to control the amount of N contained in the sulfide solid electrolyte.
[0042] A sulfide solid electrolyte according to another aspect of the present invention is a sulfide solid electrolyte produced by the above-mentioned production method. With such a sulfide solid electrolyte, the emission of N to the outside of the system during the production process of the sulfide solid electrolyte is suppressed, and therefore various effects due to the inclusion of N can be fully exhibited.
[0043] An all-solid-state battery according to another embodiment of the present invention includes a sulfide solid electrolyte produced using the raw material compounds selected by the selection method. Such a sulfide solid electrolyte suppresses the emission of N to the outside of the system during the production process, and therefore can fully exhibit various effects due to the inclusion of N.
[0044] A sulfide solid electrolyte according to another embodiment of the present invention is a sulfide solid electrolyte having a crystal structure and containing, as constituent elements, P, S, N, element A, element X, and element M. Here, A represents at least one element selected from the group consisting of Li, Na, and K. X represents at least one element selected from the group consisting of Cl, Br, and I. M represents at least one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, P, Zr, and Ti.
[0045] Such a sulfide solid electrolyte can improve the thermal stability of the HICP, as compared with a sulfide solid electrolyte consisting of only Li, P, S, N, and the element X.
[0046] It is preferable that the element M is at least one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, and B.
[0047] This makes it possible to further increase the thermal stability of the HICP.
[0048] The above crystal structure preferably has diffraction peaks at 2θ=20.2°±0.5° and 23.6°±0.5° in X-ray diffraction measurement using CuKα radiation.
[0049] When the sulfide solid electrolyte has the above crystal structure, good Li-ion conductivity can be obtained.
[0050] An all-solid-state battery according to another embodiment of the present invention is an all-solid-state battery including a sulfide solid electrolyte having a crystalline structure and containing, as constituent elements, P, S, N, element A, element X, and element M.
[0051] One advantage of solid-state batteries over non-aqueous electrolyte batteries is that they have a much higher upper operating temperature limit, due to the high thermal stability of solid electrolytes. However, Patent Documents 2 and 3 describe that a sulfide solid electrolyte containing Li, P, S, N, Br, and I undergoes a phase transition from a high Li ion conductive phase to a low Li ion conductive phase when heated to a high temperature. In other words, the operating temperature of an all-solid-state battery including such a sulfide solid electrolyte is limited by the phase transition temperature of the high Li ion conductive phase. In contrast, the sulfide solid electrolyte has higher thermal stability of HICP than conventional sulfide solid electrolytes that do not contain element M. Therefore, an all-solid-state battery including the sulfide solid electrolyte of the present invention can fully enjoy the advantage of an all-solid-state battery that can increase the upper limit of the operating temperature of the battery.
[0052] A sulfide solid electrolyte according to another embodiment of the present invention is a crystalline sulfide solid electrolyte containing P, S, N, element A, and element M. Here, A represents at least one element selected from the group consisting of Li, Na, and K. M represents at least one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, P, Zr, and Ti.
[0053] With such a sulfide solid electrolyte, the atmospheric stability can be improved by suppressing the emission of N to the outside of the system during the production process of the sulfide solid electrolyte.
[0054] It is preferable that the element M is at least one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, and B.
[0055] According to this, the emission of N to the outside of the system in the production process of the sulfide solid electrolyte can be more reliably suppressed, thereby making it possible to further improve the atmospheric stability, etc.
[0056] Hereinafter, a method for producing a sulfide solid electrolyte according to one embodiment of the present invention, a sulfide solid electrolyte, an all-solid-state battery, and a method for selecting raw material compounds used in the production of a sulfide solid electrolyte will be described in detail. Note that matters other than those specifically mentioned in this specification and necessary for carrying out the present invention can be understood as design matters of a person skilled in the art based on the prior art in the field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the field.
[0057] <Method of manufacturing sulfide solid electrolyte> [Embodiment] A method for producing a sulfide solid electrolyte according to one embodiment of the present invention includes a preparation step of preparing a composition containing P, S, N, element A, and element M, a reaction step of reacting the composition to obtain an intermediate, and a heating step of heating the intermediate to obtain a sulfide solid electrolyte, the composition including a raw material compound containing N, element A, and element M. Here, A is at least one element selected from the group consisting of Li, Na, and K. M is at least one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, P, Zr, and Ti. In this embodiment, a method for producing the sulfide solid electrolyte will be described using an example in which Li is contained as element A. Fig. 1 is a flow chart showing an example of the method for producing the sulfide solid electrolyte according to this embodiment, and the following description will be made along with this flow chart.
[0058] (preparation process) In this process, a composition containing Li, P, S, N, and element M is prepared. The composition is preferably a mixture of one or more raw material compounds containing N, Li, and element M (hereinafter also referred to as Li-MN-containing compounds) and one or more raw material compounds containing Li, P, and S.
[0059] In Figure 1, first, Li 3N and a nitride of element M are prepared and mixed in a mortar, etc. Next, pellets of the mixed raw material compounds are produced. Next, the pellets are heat-treated to produce a Li-MN-containing compound.
[0060] The means for preparing the Li-MN-containing compound is not limited to this, and the compound may be prepared by other methods. For example, the raw material for the Li-MN-containing compound may be two or more compounds containing any of N, Li, and element M. The Li-MN-containing compound may be prepared by mechanical milling. The MN-containing compound may be an industrially manufactured and commercially available compound.
[0061] As the Li-MN-containing compound, a lithium composite nitride of element M is preferably used. As the lithium composite nitride of element M, for example, Li 3 / 2 Al 1 / 2 N, Li 3 / 2 B 1 / 2 N, Li 5 / 3 S 1 / 3 N, Li 9 / 5 S 3 / 10 N, Li 7 / 4 P 1 / 4 N, LiMgN, LiHf 1 / 2 N, Li 3 / 2 Sc 1 / 2 N, LiZr 1 / 2 N, Li 5 / 3 Ti 1 / 3 N, Li 4 / 3 Ta 1 / 3 N, Li 7 / 4 Ta 1 / 4 N, Li 7 / 4 Nb 1 / 4 N, LiC 1 / 2 Among these, Li is the most popular because it is easily available. 3 / 2 Al 1 / 2 N, Li 3 / 2 B 1 / 2 N, and Li 5 / 3 S 1 / 3 N is preferred. Li 2 From the viewpoint of suppressing S precipitation, Li 3 / 2 Al 1 / 2N is particularly preferred, and Li is preferred from the viewpoint of improving the thermal stability of HICP. 3 / 2 B 1 / 2 N and Li 5 / 3 S 1 / 3 N is particularly preferred. From the viewpoint of suppressing the emission of N out of the system in the production process of the sulfide solid electrolyte, Li 3 / 2 Al 1 / 2 N and Li 3 / 2 B 1 / 2 N is particularly preferred.
[0062] Examples of the raw material compound containing element M include oxides of element M, sulfides of element M, nitrides of element M, and alloys of element M and Li. Examples of the sulfides of element M include Al. 2 S 3 , SiS 2 Examples of nitrides of element M include AlN, Si 3 N 4 , BN, Mg 3 N 2 The raw material compound containing the element M may be used alone or in combination of two or more.
[0063] The element M in the manufacturing method is not particularly limited as long as it is at least one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, P, Zr, and Ti. Among these, from the viewpoint of more reliably suppressing the discharge of N out of the system in the manufacturing process of the sulfide solid electrolyte, the element M is preferably any one of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, and P, and more preferably any one of Al, Ta, Si, Sc, Mg, Nb, and B. In addition, since it is easy to obtain, the element M is even more preferably any one of Al, Si, and B. In particular, the element M may be Al.
[0064] Examples of raw material compounds containing N include Li 3 N, P, P 3 N 5 , S 4 N 4 , S 2 N 2 , S 4N 2 Among these, Li 3 N is preferred. The raw material compound containing N may be used alone or in combination of two or more.
[0065] Examples of raw material compounds containing Li (also referred to as Li compounds) include Li 2 S., Li 2 O, Li 3 N, Li 2 CO 3 , metallic lithium, etc. Among these, Li 2 Preferred is S. The raw material compound containing Li may be used alone or in combination of two or more.
[0066] Examples of raw material compounds containing P (also referred to as P compounds) include P 2 S 3 , P 2 S 5 , P 2 O 5 , P 3 N 5 Among these, P 2 S 3 and P 2 S 5 is preferred, and P 2 S 5 The raw material compound containing P may be used alone or in combination of two or more.
[0067] Examples of raw material compounds containing S include Li 2 S, P 2 S 3 , P 2 S 5 , sulfides of element M, elemental sulfur, etc. The raw material compound containing S may be used alone or in combination of two or more.
[0068] The composition preferably contains a Li compound, a P compound, and a Li-MN-containing compound, and more preferably, at least one of the Li compound and the P compound contains S. The Li compound, the P compound, and the Li-MN-containing compound include lithium sulfide, phosphorus sulfide, and a compound represented by the general formula Li α M β It is more preferable that the compound contains a compound represented by the formula: N (α and β are values that give a stoichiometric ratio according to the type of element M).
[0069] Sulfide solid electrolytes have a high Li content. 2 The atmospheric stability is reduced due to the precipitation of S, and if the content is low, the ionic conductivity may decrease. Also, if the content of N is high, Li 2 The atmospheric stability is reduced due to precipitation of S, and if the amount is small, there is a risk that the effects of containing N, such as improving the atmospheric stability, will not be fully exhibited. From these viewpoints, it is preferable that the element ratios in the above composition in a mixed state simultaneously satisfy the following formulae in terms of molar ratio: 2.30 ≦ Li / P ≦ 4.20 0.0100≦N / P≦1.20 It is more preferable that the above Li / P and N / P simultaneously satisfy the following formulae: 2.36 ≦ Li / P ≦ 4.12 0.0200≦N / P≦1.11 It is more preferable that the Li / P and the N / P simultaneously satisfy the following formulae: 2.36 ≦ Li / P ≦ 4.00 0.0600≦N / P≦0.900 It is even more preferable that the Li / P and N / P simultaneously satisfy the following formulae: 2.60 ≦ Li / P ≦ 3.40 0.190 ≦ N / P ≦ 0.710 It is particularly preferable that the Li / P and N / P simultaneously satisfy the following formulae: 2.77 ≦ Li / P ≦ 3.38 0.280 ≦ N / P ≦ 0.650
[0070] Further, in the above composition, it is preferable that the molar ratio of each element of Li, P, S, N, and element M satisfies the general formula (100 - z)(yLi 2 S·(1 - y)P 2 S 5 )·zLi α M β N (where 0 < z ≦ 40, 0.50 ≦ y ≦ 0.75, α and β are numerical values that give a stoichiometric ratio according to the type of element M). According to this, a sulfide solid electrolyte excellent in air stability and ionic conductivity at 25°C can be produced. Note that the above general formula indicates the content ratio of Li, S, P, N, and element M, and the above composition is not specified to consist of Li 2 S, P 2 S 5 , and Li α M β N.
[0071] In the above general formula, z is preferably greater than 0 and 40 or less, and more preferably 1 or more and 30 or less. When z in the above general formula is within the above range, a sulfide solid electrolyte excellent in air stability and ionic conductivity can be produced. Further, when 1 ≦ z ≦ 30, a sulfide solid electrolyte with increased ionic conductivity at 25°C can be produced. When 10 ≦ z ≦ 40, so-called cross-linked sulfur P 2 S 7 4- (S 3 P - S - PS 3 ) decreases, and a sulfide solid electrolyte excellent in air stability that substantially does not contain Li 2 S which is easily reactive with water can be produced.
[0072] In the above general formula, y is preferably 0.50 or more and 0.75 or less, and more preferably 0.67 or more and 0.70 or less. In the above composition, Li 2 S and P 2 S 5By making the content ratio of the sulfide in the above range, it is possible to produce a sulfide solid electrolyte having an increased ionic conductivity at 25°C.
[0073] In the above general formula, α and β are numerical values that give a stoichiometric ratio depending on the type of element M. The values of α and β are not particularly limited, but may be, for example, 0.80≦α≦3.0 and 0.10≦β≦1.2.
[0074] (Reaction process) In this step, a composition containing Li, P, S, N, and element M is subjected to mechanical milling to react with the composition to obtain an intermediate. The method for obtaining the intermediate is not limited to this, and other methods may be used. For example, in FIG. 1, instead of mechanical milling, a melt quenching method or the like may be used.
[0075] Mechanical milling may be either dry or wet, but wet is preferred because it can mix the raw material compounds more uniformly. Examples of mechanical milling include container-driven mills, media-agitating mills, milling with a high-speed rotary grinder, roller mills, and jet mills. Examples of container-driven mills include rotary mills, vibration mills, and planetary mills. Examples of media-agitating mills include attritors and bead mills. Examples of milling with a high-speed rotary grinder include hammer mills and pin mills. Among these, container-driven mills are preferred, and planetary mills are particularly preferred.
[0076] The intermediate obtained in the reaction step may have a crystalline structure, but is preferably a so-called sulfide glass. "Sulfide glass" refers to a sulfide solid electrolyte containing an amorphous structure. When the intermediate is a sulfide glass, Li 2 It is possible to obtain a sulfide solid electrolyte with less crystal phases such as S that are unstable in the atmosphere and with high dispersion of N, element M, etc.
[0077] (Heat treatment process) In this process, the intermediate is heat-treated at a temperature equal to or higher than the crystallization temperature to produce a sulfide solid electrolyte. The heat treatment may be performed under a reduced pressure atmosphere or an inert gas atmosphere. The crystallization temperature can be determined by measurement using a differential scanning calorimeter (DSC). For example, Li 7 P 3 S 11 In order to obtain the crystal structure, the heat treatment temperature is preferably 250°C or higher and 400°C or lower. 3 P.S. 4 In order to obtain a crystal structure, the heat treatment temperature is preferably 200° C. or more and 400° C. or less. In addition, in order to obtain a first crystal structure having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, and 29.8°±0.5° in X-ray diffraction measurement using CuKα radiation, the heat treatment temperature is preferably 250° C. or more and 400° C. or less. This is because when heat treatment is performed at a high temperature such as 500° C., the stable phase Li 4 P 2 S 6 This is because there is a possibility of a phase transition to
[0078] [Variations] The method for producing a sulfide solid electrolyte according to the present invention is not limited to the above-described embodiment, and can be carried out in various modified and improved forms in addition to the above-described forms.
[0079] In the above embodiment, Li 2 SP 2 S 5 Although the sulfide solid electrolyte of the above-mentioned type has been described as an example, a LGPS-type sulfide solid electrolyte or an argyrodite-type sulfide solid electrolyte may also be produced by the production method. As an example of an LGPS-type sulfide solid electrolyte, Li 10 GeP 2 S 12 Li 10 GeP 2 S 12The crystal structure having this crystalline phase has diffraction peaks at 2θ=14.4°±0.5°, 20.1°±0.5°, 20.4°±0.5°, 26.9°±0.5°, 29.5°±0.5°, and 47.3°±0.5° in X-ray diffraction measurement using CuKα radiation. As an example of an argyrodite-type sulfide solid electrolyte, Li 6 P.S. 5 Examples include Cl. 6 P.S. 5 A crystal structure having a Cl crystalline phase has diffraction peaks at 2θ=15.6°±0.5°, 25.5°±0.5°, 30.0°±0.5°, 31.4°±0.5°, 45.0°±0.5°, and 52.5°±0.5° in X-ray diffraction measurement using CuKα radiation.
[0080] [Variation 1] As Modification 1, an embodiment for producing a LGPS-type sulfide solid electrolyte will be described. By adding a raw material compound containing Ge to the composition in the preparation step, a LGPS-type sulfide solid electrolyte can be produced. Examples of the raw material compound containing Ge include GeS 2 In the case of producing a LGPS type sulfide solid electrolyte, it is preferable that the composition has an element ratio in molar ratio that simultaneously satisfies the following formulas: 5.01 ≦ Li / P ≦ 5.61 0.0051 ≦ N / P ≦ 0.41 By setting the content ratio of the elements in the composition in the above range, Li 10 GeP 2 S 12 It is possible to produce a sulfide solid electrolyte having a crystal phase of high ionic conductivity at 25°C.
[0081] [Variation 2] As Modification 2, an embodiment will be described in which a sulfide solid electrolyte having a crystal structure containing, as constituent elements, Li, P, S, N, an element X, and an element M. X is at least one element selected from the group consisting of Cl, Br, and I.
[0082] In Modification 2, a raw material compound containing element X is added to the above composition to produce a crystalline sulfide solid electrolyte containing Li, P, S, N, element X, and element M. This makes it possible to produce a sulfide solid electrolyte having HICP and improved thermal stability of the HICP.
[0083] Examples of raw material compounds containing element X include lithium halides, sulfur halides, phosphorus halides, M η X σ (wherein η is 1 or 2, and σ is an integer of 1 to 10), and the like. Examples of lithium halides include LiCl, LiBr, and LiI. Examples of sulfur halides include SCl 2 , S 2 Cl 2 , SBr 2 , S 2 Br 2 , S.I. 2 , S 2 I 2 etc. Phosphorus halides include, for example, PCl 3 , PCl 5 , POCl 3 , PBr 3 , PBr 5 , POBr 3 , P.I. 3 , PCI 4 , P 2 I 4 etc. The halide of the element M is, for example, AlBr 3 , BBr 3 , AlCl 3 , AlBr 3 ,AlI 3 , SiCl 3 , SiCl 4 , SiBr 4 , SiI 4 , SiBrI 3 , SiBr 2 I 2 , SiBr 3 I, BCl3 , BBr 3 , B.I. 3 etc. Among these, lithium halides and phosphorus halides are preferred, and lithium halides are more preferred. As the lithium halides, LiBr and LiI are preferred. The raw material compound containing the element X may be used alone or in combination of two or more. The composition may contain one element X alone or two or more elements X. In particular, from the viewpoint of increasing the ionic conductivity at 25° C., it is preferable that the element X contains Br or I alone, and it is more preferable that the element X contains Br alone. It is also preferable that the element X contains Br and I simultaneously.
[0084] In variant example 2, when the composition contains Br and I simultaneously, the content of Br relative to the total amount of Br and I in the composition is preferably 1 mol% or more and 99 mol% or less, and more preferably 5 mol% or more and 80 mol% or less.
[0085] Sulfide solid electrolytes have a high Li content. 2 The atmospheric stability is reduced due to the precipitation of S, and if the content is low, HICP may not precipitate. Also, if the content of N is high, Li 2 The atmospheric stability is reduced due to precipitation of S, and if the content is low, there is a risk that the effect of containing N cannot be fully exhibited. Furthermore, if the content of element X is high, a crystalline phase of lithium halide may remain in the sulfide solid electrolyte, reducing ion conductivity, and if the content is low, there is a risk that the effect of containing element X cannot be fully exhibited. From these viewpoints, it is preferable that the composition in the preparation step of Modification 2 has element ratios in a mixed state that simultaneously satisfy the following formulas in terms of molar ratio: 3.10 ≦ Li / P ≦ 4.20 0.0600≦N / P≦0.750 0.180 ≦ X / P ≦ 1.30 Furthermore, it is more preferable that the above Li / P, the above N / P, and the above X / P simultaneously satisfy the following formulas respectively. 3.10 ≦ Li / P ≦ 3.90 0.0900 ≦ N / P ≦ 0.750 0.180 ≦ X / P ≦ 1.00
[0086] It is preferable that the molar ratios of the respective elements of Li, P, S, N, element X, and element M in the above composition satisfy the general formula (100-z){(1-y)[xLi 2 S·(1-x)P 2 S 5 ·yLi α M β N}·zLiX (where 0.50≦x≦0.80, 0<y≦0.50, 5≦z≦40, α and β are numerical values giving stoichiometric ratios according to the type of element M). More preferably, x, y, and z are 0.67≦x≦0.73, 0.10≦y≦0.30, and 10≦z≦30 respectively. Thereby, the thermal stability of HICP can be improved. Furthermore, when the above composition contains two types of element X as element X 1 and X 2 the above general formula can also be expressed as (100-z 1 -z 2 ){(1-y)[xLi 2 S·(1-x)P 2 S 5 ·yLi α M β N}·z 1 LiX 1 ·z 2 LiX 2 (where 0.50≦x≦0.80, 0<y≦0.50, 5≦(z 1 +z 2 )≦40, α and β are numerical values giving stoichiometric ratios according to the type of element M). In this case, x, y, z 1 and z 2 are preferably 0.67≦x≦0.73, 0.10≦y≦0.30, and 10≦(z 1 +z 2 )≦30 respectively. Note that the above general formula indicates the content ratios of Li, S, P, N, element M, and element X, and the above composition contains Li 2 S, P 2 S 5 and Li α M β N, and LiX does not specify that it consists of these components.
[0087] In the above general formula, when element M is either Al or B, α = 2 / 3 and β = 1 / 2 may be applicable. In this case, x, y, and z are preferably 0.50 ≦ x ≦ 0.80, 0 < y ≦ 0.50, and 5 ≦ z ≦ 40, more preferably 0.60 ≦ x ≦ 0.75, 0.050 ≦ y ≦ 0.40, and 10 ≦ z ≦ 30, and even more preferably 0.67 ≦ x ≦ 0.73, 0.10 ≦ y ≦ 0.30, and 15 ≦ z ≦ 25.
[0088] The raw materials used in the reaction process of Modification Example 2 preferably include a Li compound, a P compound, a halogen compound, and a Li-M-N-containing compound, and it is more preferable that at least one of the above Li compound and the above P compound contains an S element. Further, as the above Li compound, the above P compound, the above halogenated compound, and the above Li-M-N-containing compound, lithium sulfide, phosphorus sulfide, lithium halide, and a compound represented by the general formula Li α M β N (α and β are numerical values giving the stoichiometric ratio according to the type of element M) are more preferably contained.
[0089] In the heat treatment step of Modification Example 2, a sulfide solid electrolyte is produced by heat-treating the intermediate at a temperature equal to or higher than the crystallization temperature. The heat treatment may be performed under a reduced pressure atmosphere or under an inert gas atmosphere. The crystallization temperature can be determined by measurement using a differential scanning calorimeter (DSC).
[0090] In Modification Example 2, a sulfide solid electrolyte having HICP is produced. After HICP undergoes a phase transition to either LICP or a specific crystal structure C, it further becomes β-Li 3 PS 4Of these crystal phases, HICP has the highest ionic conductivity. Therefore, in the heat treatment process in the second modification, the lower limit of the heat treatment temperature is the HICP generation temperature T H The upper limit of the heat treatment temperature is preferably β-Li 3 P.S. 4 The formation temperature T β It is preferable that the LICP generation temperature T L or the formation temperature T of a specific crystal structure C C It is more preferable that the value is less than or equal to T H , T L , T C and T β can be determined by XRD measurement. The sulfide solid electrolyte produced in the second modification is T β -T H But, T β -T H ≧40° C., and T β -T H More preferably, T is ≧50° C. β -T H More preferably, T is ≧60° C. β -T H It is particularly preferred that it is ≧70° C.
[0091] The sulfide solid electrolyte produced in Modification 2 has a wide heat treatment temperature range in which ionic conductivity does not decrease. In other words, even if the heat treatment temperature deviates from the intended temperature in the heat treatment step, there is little risk of the ionic conductivity of the produced sulfide solid electrolyte decreasing. Therefore, Modification 2 has the advantage that a sulfide solid electrolyte with high ionic conductivity can be produced without requiring strict temperature control in the heat treatment step.
[0092] In addition, "HICP" represents a crystal phase having diffraction peaks at 2θ=20.2°±0.5° and 23.6°±0.5° in X-ray diffraction measurement using CuKα radiation. This crystal structure is a crystal phase described in Patent Document 2 and the like, and is a crystal phase with high Li-ion conductivity. "LICP" represents a crystal phase having diffraction peaks at 2θ=21.0°±0.5° and 28.0°±0.5° in X-ray diffraction measurement using CuKα radiation. This crystal structure is a crystal phase described in Patent Document 2 and the like, and is a crystal phase with low Li-ion conductivity. "Specific crystal structure C" represents a crystal phase having diffraction peaks at 2θ=17.5°±0.5° and 24.9°±0.5° in X-ray diffraction measurement using CuKα radiation. "β-Li 3 P.S. 4 " represents a crystalline phase having diffraction peaks at 2θ=17.5°±0.5°, 18.1°±0.5°, 29.1°±0.5°, 29.9°±0.5°, and 31.2°±0.5° in X-ray diffraction measurement using CuKα radiation.
[0093] The X-ray diffraction measurement using CuKα radiation in this specification is carried out according to the following procedure. The solid electrolyte powder to be measured is filled into an airtight sample holder for X-ray diffraction measurement in an argon atmosphere with a dew point of -50°C or less. Powder X-ray diffraction measurement is carried out using an X-ray diffraction device (Rigaku's "MiniFlex II"). The radiation source is CuKα radiation, the tube voltage is 30 kV, the tube current is 15 mA, and the diffracted X-rays are passed through a 30 μm thick Kβ filter and detected by a high-speed one-dimensional detector (model number: D / teX Ultra 2). The sampling width is 0.01°, the scan speed is 5° / min, the divergence slit width is 0.625°, the receiving slit width is 13 mm (OPEN), and the scattering slit width is 8 mm.
[0094] <How to select raw material compounds> According to the method for producing a sulfide solid electrolyte of the present invention, by using a raw material compound containing N, element A, and element M, it is possible to suppress the release of N to the outside of the system during the production process of the sulfide solid electrolyte. In selecting element A and element M that provide such an effect, the present inventors used first-principles calculations. Hereinafter, a method for selecting raw material compounds used in the production of a sulfide solid electrolyte according to one embodiment of the present invention will be described.
[0095] In this embodiment, the raw material compounds are selected according to the procedures (1) to (3). (1) A candidate material is selected that contains N, an element A', and an element M', and the first neighboring atoms of the element A' and the element M' are N. (2) Using first-principles calculations, we have determined the defect formation energy E Ndefect Calculate. (3) E above Ndefect is 4.00 eV or more, the candidate material is selected as the raw material compound.
[0096] First-principles calculation is a calculation method for predicting physical properties non-empirically, and is a method capable of calculating the total energy and the energy band structure of electrons of a model including atoms whose atomic numbers and spatial coordinates are known. Calculating the forces acting on atoms enables structural optimization, and also allows the calculation of lattice constants, stable structures at 0 K, band gaps, etc. Calculation methods are broadly divided into two types: "wave function theory" and "density functional theory." The calculation method used in this specification is based on density functional theory.
[0097] N defect formation energy E Ndefect is the energy value required to remove N from the crystal structure and generate a defect. The defect formation energy of N is the total energy E of a crystal structure without defects. perfect and the total energy E of the crystal structure containing N defects Nvacancy and the chemical potential μ of the N atom N and is defined by the following formula (1). E Ndefect = ( E Nvacancy + μ N ) - E perfect Formula (1) That is, the defect formation energy E Ndefect The procedure for calculating is as follows: (a) Obtain the composition and crystal structure of the candidate material. (b) Chemical potential μ of the N atom desorbed as a defect N Calculate. (c) The total energy E of a defect-free crystal structure perfect is calculated by structural optimization calculation. (d) Total energy E of a crystal structure containing N defects Nvacancy is calculated by structural optimization calculation. (e) The defect formation energy E of N according to equation (1) Ndefect Calculate. If there are multiple N-occupied sites in the crystal structure of the candidate material, E Ndefect The lowest value is the E of the candidate material. Ndefect Used as. The composition and crystal structure of the candidate material can be arbitrarily selected from those available in publicly known publications, databases, etc. The candidate material is not particularly limited as long as it is a compound containing N, element A', and element M', but is preferably a compound that is stable at room temperature and normal pressure.
[0098] In this embodiment, the element A' is a metal element. The element M' is an element other than nitrogen that belongs to any one of Groups 2 to 15 of the periodic table and is different from the element A'. N is a nitrogen element. The element A' is not particularly limited, but is preferably any one of an alkali metal element, an alkaline earth metal element, and an aluminum element, more preferably at least one selected from Li, Na, K, Mg, Ca, and Al, and even more preferably Li, which makes it easy to operate the sulfide solid electrolyte as a battery.
[0099] In this embodiment, Li α M´ β N (α and β are values that give the stoichiometric ratio depending on the type of element M), and Li 3The defect formation energy of N was calculated. In other words, Li was selected as element A'. As element M', B, Mg, Al, Si, P, Ca, Sr, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, Ge, Sr, Y, Zr, Nb, In, Sn, Ce, Hf, Ta, and C were evaluated. The first-principles calculations were performed using the Vienna Ab-initio Simulation Package (VASP) software. The calculation conditions were as follows: The k-point was set so that the k-resolution value was approximately 1000. The k-resolution is the product of the number of atoms in the model and the k-points in the a, b, and c axis directions. Cutoff energy of plane wave basis functions: 520 eV Approximation method for exchange-correlation interaction: GGA+U Pseudopotential: PAW(PBEsol) k point:k-resolution≒1000 Convergence condition for SCF calculation: 10 -4 eV Occupancy rate of each atomic site (Occ.): 1 The 3d orbital is the outermost orbital, and in the state of a cation with a stable valence, the 3d orbital is not a closed shell, and electrons exist in the 3d orbital. For the first-principles calculation of materials containing V, Cr, Mn, Fe, Co, and Ni, the Hubbard U eff The values were used as calculation conditions. This allowed the localization effect of electrons in the d orbitals to be reflected in the calculation. eff The values are taken from the calculation conditions of the first-principles calculations carried out in the crystal structure database Materials Project (https: / / materialsproject.org / #search / materials) (as of August 22, 2019). By searching the database for materials containing V, Cr, Mn, Fe, Co, and Ni, eff The value was obtained.
[0100] [Table 1]
[0101] In step (d) above, in order to reduce interactions between N defects, the calculation model cell was designed so that the lattice constants a, b, and c were all approximately 10 Å, with the total number of atoms not exceeding 200. Table 2 shows the lattice constants used in the calculations for some of the candidate materials.
[0102] [Table 2]
[0103] Table 3 shows the element M´, the chemical composition of each candidate material, and the defect formation energy E Ndefect Shows.
[0104] [Table 3]
[0105] From Table 3, Li 3 The defect formation energy E of N in N Ndefect It can be seen that the energy is 2.94 eV. In addition, the elements V, Y, Ga, Ca, Ce, Sn, Zn, Ge, Cr, Mn, Sr, In, Co, Ni, and Fe are Li α M´ β The defect formation energy E of N in N Ndefect It can be seen that the potential difference is small, at 3.88 eV or less. For this reason, in a candidate material containing any of V, Y, Ga, Ca, Ce, Sn, Zn, Ge, Cr, Mn, Sr, In, Co, Ni, and Fe as the element M', N defects are likely to be generated, and it is predicted that the effect of the present invention of suppressing the emission of N to the outside of the system in the production process of the sulfide solid electrolyte will not be obtained or the effect will be small. On the other hand, the elements Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, P, Zr, and Ti are α M´ β The defect formation energy E of N in N NdefectIt can be seen that the value of the valence energy of the sulfide solid electrolyte is large, being 4.00 eV or more. Therefore, it is predicted that if the candidate material contains any one of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, P, Zr, and Ti as the element M', N defects are unlikely to be generated, and the effect of the present invention, which suppresses the emission of N to the outside of the system in the production process of the sulfide solid electrolyte, is highly likely to be exhibited.
[0106] The candidate materials are those with the defect formation energy E Ndefect It is predicted that the larger the value of is, the less likely N defects are to be generated, and the emission of N to the outside of the system in the production process of the sulfide solid electrolyte can be further suppressed. For this reason, in this embodiment, the defect generation energy E of N of the candidate material is Ndefect is 4.00 eV or more, preferably 4.10 eV or more, more preferably 4.20 eV or more, even more preferably 4.30 eV or more, and particularly preferably 4.35 eV or more.
[0107] In this embodiment, the calculation was performed for the case where the element A′ contains Li. α M´ β The first-principles calculation was performed using N as a model. However, the present invention is not limited to this. The element A' may be any metal element, and for example, a candidate material containing any of Na, K, Mg, Ca, and Al may be selected as the element A', and a raw material compound may be selected using the first-principles calculation.
[0108] <Sulfide solid electrolyte> [Embodiment 1] A sulfide solid electrolyte according to one embodiment of the present invention is a composition containing P, S, N, element A, and element M, and is produced by a production method including: preparing raw material compounds containing N, element A, and element M; reacting the composition to obtain an intermediate; and heating the intermediate to obtain a sulfide solid electrolyte. Hereinafter, the sulfide solid electrolyte will be described using an example in which element A contains Li.
[0109] The sulfide solid electrolyte has a crystalline structure. The term "crystalline structure" means that a peak derived from the crystalline structure of the sulfide solid electrolyte is observed in an X-ray diffraction pattern in an X-ray diffraction measurement. The sulfide solid electrolyte may contain an amorphous portion.
[0110] The crystal structure of the sulfide solid electrolyte may be, for example, HICP, LGPS type, argyrodite type, Li 7 P 3 S 11 Among these, the crystal structures are HICP, LGPS type, Argyrodite type, and Li 7 P 3 S 11 Among these, Li is preferred because it has high stability against Li. 7 P 3 S 11 From the viewpoint of stability against the atmosphere, Li 4 P 2 S 6 or β-Li 3 P.S. 4 or a first crystal structure having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, and 29.8°±0.5° in X-ray diffraction measurement using CuKα radiation, and among these, the first crystal structure having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, and 29.8°±0.5° in X-ray diffraction measurement using CuKα radiation is more preferable because of its high lithium ion conductivity.
[0111] The first crystal structure may include a specific crystal structure A having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, 29.8°±0.5°, and 30.9°±0.5° in the X-ray diffraction measurement, or a specific crystal structure B having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, and 29.8°±0.5° but no diffraction peak at 30.9°±0.5° in the X-ray diffraction measurement. With the above configuration, a sulfide solid electrolyte capable of increasing the initial coulombic efficiency of an all-solid-state battery including the solid electrolyte is obtained.
[0112] The diffraction peak in the first crystal structure may have a 2θ range within ±0.3°, or may have a 2θ range within ±0.1°.
[0113] The above Li 7 P 3 S 11 The crystal structure having this crystalline phase has diffraction peaks at 2θ=17.8°±0.5°, 18.5°±0.5°, 23.7°±0.5°, 29.6°±0.5°, and 30.0°±0.5° in X-ray diffraction measurement using CuKα radiation.
[0114] The LGPS-type sulfide solid electrolyte may be, for example, Li 10 GeP 2 S 12 Li 10 GeP 2 S 12 The crystal structure having this crystalline phase has diffraction peaks at 2θ=14.4°±0.5°, 20.1°±0.5°, 20.4°±0.5°, 26.9°±0.5°, 29.5°±0.5°, and 47.3°±0.5° in X-ray diffraction measurement using CuKα radiation.
[0115] The argyrodite-type sulfide solid electrolyte is, for example, Li 6 P.S. 5 Examples include Cl. 6 P.S. 5A crystal structure having a Cl crystalline phase has diffraction peaks at 2θ=15.6°±0.5°, 25.5°±0.5°, 30.0°±0.5°, 31.4°±0.5°, 45.0°±0.5°, and 52.5°±0.5° in X-ray diffraction measurement using CuKα radiation.
[0116] The above Li 4 P 2 S 6 The crystal structure having this crystal phase has diffraction peaks at 2θ=16.9°±0.5°, 27.1°±0.5°, 32.1°±0.5°, and 32.5°±0.5° in X-ray diffraction measurement using CuKα radiation.
[0117] The above β-Li 3 P.S. 4 The crystal structure having this crystalline phase has diffraction peaks at 2θ=17.5°±0.5°, 18.1°±0.5°, 29.1°±0.5°, 29.9°±0.5°, and 31.2°±0.5° in X-ray diffraction measurement using CuKα radiation.
[0118] The sulfide solid electrolyte preferably contains a so-called ortho-composition anion structure as a main component. For example, the sulfide solid electrolyte may contain Li 2 SP 2 S 5 In the case of PS-based solid electrolytes, 4 3- It is preferable that the polymer contains the structure as a main component. Here, the term "main component" means that the proportion of a specific component in the total components is 50 mol % or more.
[0119] When the sulfide solid electrolyte contains an anion structure with an ortho composition as a main component, the content of the anion structure with an ortho composition relative to all anion structures constituting the sulfide solid electrolyte is 50 mol% or more and less than 100 mol%, preferably 60 mol% or more and less than 100 mol%, more preferably 70 mol% or more and less than 100 mol%, even more preferably 80 mol% or more and less than 100 mol%, and particularly preferably 90 mol% or more and less than 100 mol%.
[0120] It is preferable that the sulfide solid electrolyte does not substantially contain bridging sulfur. Since bridging sulfur reacts with water to generate hydrogen sulfide, the atmospheric stability can be improved by substantially not containing bridging sulfur. For example, when the sulfide solid electrolyte is Li 2 SP 2 S 5 In the case of S-based solid electrolytes, 3 PS-PS 3 It is preferable that the polymer is substantially free of such structure. The fact that the compound is substantially free of bridging sulfur can be confirmed by the fact that no peak corresponding to a bridging sulfur structure is detected when a Raman spectrum is measured using a laser with an excitation wavelength of 532 nm. For example, S 3 PS-PS 3 The fact that the structure is substantially free of the substance is that when the Raman spectrum is measured with a laser having an excitation wavelength of 532 nm, the structure is substantially free of the substance. -1 This can be confirmed by the absence of a peak at The sulfide solid electrolyte may contain a small amount of bridging sulfur. In this case, the intensity I of the peak attributed to the anion structure of the ortho composition in the Raman spectroscopy measurement is O Intensity of peaks assigned to bridging sulfur relative to I P Ratio I P / I O is preferably 0.7 or less, more preferably 0.5 or less, and even more preferably 0.35 or less. For example, when the sulfide solid electrolyte is Li 2 SP 2 S 5 In the case of PS-based solid electrolytes, 4 3- 417cm due to structure -1 The peak intensity at I O corresponds to S 3 PS-PS 3 402cm due to structure -1 The peak intensity at I P is equivalent to.
[0121] The sulfide solid electrolyte is Li 2 It is preferable that S is not substantially contained.2 S reacts with water to produce hydrogen sulfide, so Li 2 By substantially not including S, the atmospheric stability can be improved. 2 "Substantially free of S" means that the material does not contain a crystal structure having diffraction peaks at 2θ=27.0±0.5°, 31.2±0.5°, 44.8±0.5°, and 53.1±0.5° in X-ray diffraction measurement using CuKα radiation.
[0122] Sulfide solid electrolytes have a high Li content. 2 The atmospheric stability is reduced due to the precipitation of S, and if the content is low, the ionic conductivity may decrease. Also, if the content of N is high, Li 2 The atmospheric stability is reduced due to precipitation of S, and if the amount is small, there is a risk that the effects of containing N, such as improving the atmospheric stability, will not be fully exhibited. From these viewpoints, it is preferable that the sulfide solid electrolyte simultaneously satisfies the following formulas in terms of element ratio by molar ratio. 2.30 ≦ Li / P ≦ 4.20 0.0100≦N / P≦1.20 It is more preferable that the above Li / P and N / P simultaneously satisfy the following formulae: 2.36 ≦ Li / P ≦ 4.12 0.0200≦N / P≦1.11 It is more preferable that the Li / P and the N / P simultaneously satisfy the following formulae: 2.36 ≦ Li / P ≦ 4.00 0.0600≦N / P≦0.900 It is even more preferable that the Li / P and N / P simultaneously satisfy the following formulae: 2.60 ≦ Li / P ≦ 3.40 0.190 ≦ N / P ≦ 0.710 It is particularly preferable that the Li / P and N / P simultaneously satisfy the following formulae: 2.77 ≦ Li / P ≦ 3.38 0.280 ≦ N / P ≦ 0.650
[0123] As the sulfide solid electrolyte, it preferably has a composition represented by the general formula (100 - z)(yLi 2 S·(1 - y)P 2 S 5 )·zLi α M β N (where 0 < z ≤ 40, 0.50 ≤ y ≤ 0.75, and α and β are numerical values that give the stoichiometric ratio according to the type of element M). By having the sulfide solid electrolyte have the composition represented by the above general formula, the air stability and the ionic conductivity at 25°C can be improved. Note that the above general formula shows the content ratios of Li, S, P, N, and element M, and the above composition does not specify that the composition consists of Li 2 S, P 2 S 5 , and Li α M β N.
[0124] As the lower limit of the ionic conductivity of the sulfide solid electrolyte at 25°C, 0.4×10 -3 S / cm is preferable, 1.0×10 -3 S / cm is more preferable, and 1.5×10 -3 S / cm is even more preferable. By having the ionic conductivity of the sulfide solid electrolyte at 25°C within the above range, the rate characteristics of the all-solid-state battery can be improved.
[0125] Note that the ionic conductivity of the sulfide solid electrolyte at 25°C is obtained by measuring the alternating current impedance by the following method. In an argon atmosphere with a dew point of -50°C or lower, after putting 120 mg of sample powder into a powder molding die with an inner diameter of 10 mm, uniaxially press-mold it using a hydraulic press at a pressure of 50 MPa or less per sample area. After releasing the pressure, after putting SUS316L powder as a current collector on the upper and lower surfaces of the sample, uniaxially press-mold it at a pressure of 360 MPa per pellet area for 5 minutes to obtain a pellet for measuring ionic conductivity. Insert this pellet for measuring ionic conductivity into an HS cell manufactured by Hokusen Co., Ltd. and perform alternating current impedance measurement. The measurement conditions are an applied voltage amplitude of 20 mV, a frequency range from 1 MHz to 100 mHz, and a measurement temperature of 25°C.
[0126] Thus, the sulfide solid electrolyte can be suitably used as a solid electrolyte for an all-solid-state battery.
[0127] [Embodiment 2] A sulfide solid electrolyte according to another embodiment of the present invention contains Li, P, S, N, an element X, and an element M. The element X represents at least one element selected from the group consisting of Cl, Br, and I.
[0128] The sulfide solid electrolyte may contain one element selected from the group consisting of Al, B, and Si as the element M, or may contain Al as the element M.
[0129] When the Li content is high, the sulfide solid electrolyte 2 The atmospheric stability is reduced due to the precipitation of S, and if the content is low, HICP may not precipitate. Also, if the content of N is high, Li 2 The atmospheric stability is reduced due to precipitation of S, and if the content is low, there is a risk that the effect of containing N cannot be fully exhibited. Furthermore, if the content of element X is high, a crystalline phase of lithium halide may remain in the sulfide solid electrolyte, reducing ion conductivity, and if the content is low, there is a risk that the effect of containing element X cannot be fully exhibited. In view of these circumstances, in the sulfide solid electrolyte, it is preferable that the content ratio Li / P of Li to the P, the content ratio N / P of N to the P, and the content ratio X / P of X to the P each simultaneously satisfy the following formulas in terms of molar ratio. 3.10 < Li / P < 4.20 0.0600 < N / P < 0.750 0.180 < X / P < 1.30 It is more preferable that the Li / P, N / P, and X / P simultaneously satisfy the following formulae: 3.10 < Li / P < 3.90 0.0900 < N / P < 0.750 0.180 < X / P < 1.00
[0130] The sulfide solid electrolyte preferably has a composition represented by the general formula (100 - z){(1 - y)[xLi 2 S·(1 - x)P 2 S 5 ·yLi α M β N}·zLiX (where 0.50 ≤ x ≤ 0.80, 0 < y ≤ 0.50, 5 ≤ z ≤ 40, α and β are numerical values that give the stoichiometric ratio according to the type of element M), and more preferably x, y, and z are 0.67 ≤ x ≤ 0.73, 0.10 ≤ y ≤ 0.30, and 10 ≤ z ≤ 30, respectively. By having the composition represented by the above general formula, the thermal stability of HICP can be improved. Further, when the sulfide solid electrolyte contains two types of elements X1 and X2 as element X, the above general formula is (100 - z 1 -z 2 ){(1 - y)[xLi 2 S·(1 - x)P 2 S 5 ·yLi α M β N}·z 1 LiX 1 ·z 2 LiX 2 (where 0.50 ≤ x ≤ 0.80, 0 < y ≤ 0.50, 5 ≤ (z 1 +z 2 ) ≤ 40, α and β are numerical values that give the stoichiometric ratio according to the type of element M), and in this case, x, y, z 1 and z 2 are preferably 0.67 ≤ x ≤ 0.73, 0.10 ≤ y ≤ 0.30, and 10 ≤ (z 1 +z 2 ) ≤ 30, respectively. Note that the above general formula indicates the content ratios of Li, S, P, N, element M, and element X, and the above composition does not specify that the composition consists of Li 2 S, P 2 S 5 , Li α M β N, and LiX.
[0131] In the above general formula, when the element M is any one of Al, B, and Sc, α may be 2 / 3 and β may be 1 / 2. In this case, x, y, and z are preferably 0.50 ≦ x ≦ 0.80, 0 < y ≦ 0.50, and 5 ≦ z ≦ 40, more preferably 0.60 ≦ x ≦ 0.75, 0.050 ≦ y ≦ 0.40, and 10 ≦ z ≦ 30, and even more preferably 0.67 ≦ x ≦ 0.73, 0.10 ≦ y ≦ 0.30, and 15 ≦ z ≦ 25.
[0132] The sulfide solid electrolyte preferably contains Br or I alone as the element X, and more preferably contains Br alone. It is also preferable to contain Br and I simultaneously. When the sulfide solid electrolyte contains Br and I simultaneously, the content of Br with respect to the total amount of Br and I contained in the sulfide solid electrolyte is preferably 1 mol% or more and 99 mol% or less, and more preferably 5 mol% or more and 80 mol% or less.
[0133] The sulfide solid electrolyte preferably contains HICP. That is, it preferably contains a crystal structure having diffraction peaks at 2θ = 20.2° ± 0.5° and 23.6° ± 0.5° in X-ray diffraction measurement using CuKα radiation.
[0134] The sulfide solid electrolyte preferably does not contain LICP. That is, it preferably does not contain a crystal structure having diffraction peaks at 2θ = 21.0° ± 0.5° and 28.0° ± 0.5° in X-ray diffraction measurement using CuKα radiation. The sulfide solid electrolyte may contain a small amount of LICP. In this case, the diffraction peak intensity ratio I H of 2θ = 20.2° ± 0.5° to the diffraction peak intensity I L of 2θ = 21.0° ± 0.5° in X-ray diffraction measurement using CuKα radiation L / I H is preferably 0 < I L / I H < 3.2, and more preferably 0 < I L / I H<2.5 is more preferable, 0 L / I H <2.0 is more preferable, and 0 L / I H It is even more preferable that the diffraction peak intensity ratio I L / I H indicates the abundance ratio of HICP and LICP contained in the sulfide solid electrolyte. In other words, the diffraction peak intensity ratio I L / I H A small value indicates that the amount of LICP is relatively small compared to HICP.
[0135] The ionic conductivity of the sulfide solid electrolyte of embodiment 2 at 25° C. is 2.0×10 -3 S / cm or more is preferable, and 2.5×10 -3 More preferably, it is 3.0×10 S / cm or more. -3 More preferably, the thickness is 4.0×10 S / cm or more. -3 With the above-mentioned configuration, the high-rate discharge performance of an all-solid-state battery including the sulfide solid electrolyte can be improved.
[0136] <All-solid-state battery> The all-solid-state battery includes an anode layer, a solid electrolyte layer, and a cathode layer. FIG. 2 is a schematic cross-sectional view showing an all-solid-state battery according to an embodiment of the present invention. In an all-solid-state battery 10, which is a secondary battery, an anode layer 1 and a cathode layer 2 are arranged with a solid electrolyte layer 3 interposed therebetween. The anode layer 1 includes an anode substrate layer 4 and an anode mixture layer 5, and the anode substrate layer 4 is the outermost layer of the anode layer 1. The cathode layer 2 includes a cathode substrate layer 7 and a cathode mixture layer 6, and the cathode substrate layer 7 is the outermost layer of the cathode layer 2. In the all-solid-state battery 10 shown in FIG. 2, the cathode mixture layer 6, the solid electrolyte layer 3, the anode mixture layer 5, and the anode substrate layer 4 are laminated in this order on the cathode substrate layer 7.
[0137] In the all-solid-state battery, the anode layer 1, the solid electrolyte layer 3, the cathode layer 2, or a combination thereof contains the sulfide solid electrolyte. In the all-solid-state battery, the anode layer 1, the solid electrolyte layer 3, the cathode layer 2, or a combination thereof contains the sulfide solid electrolyte, and therefore the initial coulombic efficiency is excellent. Since the sulfide solid electrolyte has excellent resistance to reduction, it is preferable that the anode layer 1 and / or the solid electrolyte layer 3 contain the sulfide solid electrolyte. With the above configuration, the effect of the present invention is further improved.
[0138] The all-solid-state battery may use a solid electrolyte other than the sulfide solid electrolyte in combination. The other solid electrolyte may be a sulfide solid electrolyte other than the sulfide solid electrolyte, or may be an oxide-based solid electrolyte, a dry polymer electrolyte, a gel polymer electrolyte, or a pseudo-solid electrolyte.
[0139] As the sulfide solid electrolyte other than the sulfide solid electrolyte, it is preferable that the Li ion conductivity is high. For example, Li 2 SP 2 S 5 , Li 2 SP 2 S 5 - LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 SP 2 S 5 -Li 3 N, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S 5 - LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -Z m S 2n (where m and n are positive numbers, and Z is Ge, Zn, or Ga.) Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li δ XO ε (where δ and ε are positive numbers, and X is P, Si, Ge, B, Al, Ga, or In.) Li 10 GeP 2 S 12 Among these, Li 2 SP 2 S 5 Or, Li 10 GeP 2 S 12 etc. are preferred. 2 SP 2 S 5 As for xLi 2 S·(100-x)P 2 S 5 (70≦x≦80) is preferred.
[0140] [Negative electrode layer] The negative electrode layer 1 includes a negative electrode substrate layer 4 and a negative electrode mixture layer 5 laminated on the surface of the negative electrode substrate layer 4. The negative electrode layer 1 may have an intermediate layer (not shown) between the negative electrode substrate layer 4 and the negative electrode mixture layer 5.
[0141] (Negative electrode base material layer) The negative electrode substrate layer 4 is a layer having electrical conductivity. The material of the negative electrode substrate layer 4 is not limited as long as it is an electrical conductor. For example, one or more metals selected from the group consisting of copper, aluminum, titanium, nickel, tantalum, niobium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, gold, silver, iron, platinum, chromium, tin, indium, alloys containing one or more of these metals, and stainless steel alloys can be used.
[0142] The lower limit of the average thickness of the negative electrode base layer 4 is preferably 3 μm, more preferably 5 μm, and even more preferably 8 μm. The upper limit of the average thickness of the negative electrode base layer 4 is preferably 200 μm, more preferably 100 μm, and even more preferably 50 μm. By setting the average thickness of the negative electrode base layer 4 to the above lower limit or more, the strength of the negative electrode base layer 4 can be sufficiently increased, and the negative electrode layer 1 can be formed well. By setting the average thickness of the negative electrode base layer 4 to the above upper limit or less, the volume of the other components can be sufficiently secured.
[0143] (Negative electrode mixture layer) The negative electrode mixture layer 5 can be formed from a so-called negative electrode mixture containing a negative electrode active material. The negative electrode mixture may contain a negative electrode mixture or a negative electrode composite containing a negative electrode active material and the sulfide solid electrolyte. The negative electrode mixture may contain optional components such as a solid electrolyte other than the sulfide solid electrolyte, a conductive agent, a binder, and a filler, as necessary.
[0144] <Negative electrode active material> As the negative electrode active material, a material capable of absorbing and releasing lithium ions is usually used.Specific examples of the negative electrode active material include metallic lithium, metals or semimetals such as Si and Sn, metal oxides or semimetal oxides such as Si oxide and Sn oxide, polyphosphate compounds, carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon), and lithium metal composite oxides such as lithium titanate.
[0145] The lower limit of the content of the negative electrode active material in the negative electrode mixture is preferably 10% by mass, more preferably 15% by mass. The upper limit of the content of the negative electrode active material is preferably 60% by mass, more preferably 70% by mass, even more preferably 80% by mass, particularly preferably 90% by mass, and may be 95% by mass. By setting the content of the negative electrode active material within the above range, the electric capacity of the all-solid-state battery can be increased.
[0146] <Negative Electrode Mixture or Negative Electrode Composite> The negative electrode mixture is a mixture prepared by mixing the negative electrode active material and the sulfide solid electrolyte by mechanical milling, etc. For example, the mixture of the negative electrode active material and the sulfide solid electrolyte can be obtained by mixing a particulate negative electrode active material and a particulate sulfide solid electrolyte. Examples of the negative electrode composite include a composite having a chemical or physical bond between the negative electrode active material and the sulfide solid electrolyte, a composite in which the negative electrode active material and the sulfide solid electrolyte are mechanically composited, etc. The composite is a composite in which the negative electrode active material and the sulfide solid electrolyte are present in one particle, and examples of the composite include a composite in which the negative electrode active material and the sulfide solid electrolyte form an aggregated state, a composite in which the sulfide solid electrolyte-containing coating is formed on at least a part of the surface of the negative electrode active material, etc. The negative electrode mixture or negative electrode composite may contain a solid electrolyte other than the sulfide solid electrolyte. The negative electrode active material contained in the negative electrode mixture and the sulfide solid electrolyte constitute a negative electrode mixture or a negative electrode composite, which can improve ionic conductivity.
[0147] When the negative electrode mixture contains a solid electrolyte, the lower limit of the content of the solid electrolyte in the negative electrode mixture may be 5 mass%, and preferably 10 mass%. The upper limit of the content of the solid electrolyte in the negative electrode mixture is preferably 90 mass%, more preferably 85 mass%, further preferably 80 mass%, and particularly preferably 75 mass%. By setting the content of the solid electrolyte within the above range, the electric capacity of the all-solid-state battery can be increased. The negative electrode mixture may contain the sulfide solid electrolyte, or may contain a solid electrolyte other than the sulfide solid electrolyte.
[0148] <Other optional ingredients> The conductive agent is not particularly limited. Examples of such conductive agents include natural or artificial graphite, carbon black such as furnace black, acetylene black, and ketjen black, metals, and conductive ceramics. The conductive agent may be in the form of a powder or fiber. The content of the conductive agent in the negative electrode mixture may be, for example, 0.5% by mass or more and 30% by mass or less. The negative electrode mixture may not contain a conductive agent.
[0149] The binder (binding agent) is not particularly limited, and examples thereof include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyimide, and polyacrylic acid; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.
[0150] The filler is not particularly limited, and examples of the main component of the filler include polyolefins such as polypropylene and polyethylene, silica, alumina, zeolite, glass, and carbon.
[0151] The lower limit of the average thickness of the negative electrode mixture layer 5 is preferably 30 μm, more preferably 60 μm. The upper limit of the average thickness of the negative electrode mixture layer 5 is preferably 1000 μm, more preferably 500 μm, and even more preferably 200 μm. By setting the average thickness of the negative electrode mixture layer 5 to the above lower limit or more, an all-solid-state battery having a high energy density can be obtained. By setting the average thickness of the negative electrode mixture layer 5 to the above upper limit or less, an all-solid-state battery having a negative electrode with excellent rate characteristics and high active material utilization can be obtained.
[0152] (Middle class) The intermediate layer is a coating layer on the surface of the negative electrode base material layer 4, and contains conductive particles such as carbon particles to reduce the contact resistance between the negative electrode base material layer 4 and the negative electrode mixture layer 5. The configuration of the intermediate layer is not particularly limited, and can be formed, for example, from a composition containing a resin binder and conductive particles.
[0153] [Positive electrode layer] The positive electrode layer 2 includes a positive electrode substrate layer 7 and a positive electrode mixture layer 6 laminated on the surface of the positive electrode substrate layer 7. Like the negative electrode layer 1, the positive electrode layer 2 may have an intermediate layer between the positive electrode substrate layer 7 and the positive electrode mixture layer 6. This intermediate layer may have the same configuration as the intermediate layer of the negative electrode layer 1.
[0154] (Positive electrode substrate layer) The positive electrode substrate layer 7 may have the same configuration as the negative electrode substrate layer 4. The material of the positive electrode substrate layer 7 is not limited as long as it is a conductor. For example, it may be one or more metals selected from the group consisting of copper, aluminum, titanium, nickel, tantalum, niobium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, gold, silver, iron, platinum, chromium, tin, indium, and alloys containing one or more of these metals, and stainless steel alloys.
[0155] The lower limit of the average thickness of the positive electrode substrate layer 7 is preferably 3 μm, more preferably 5 μm. The upper limit of the average thickness of the positive electrode substrate layer 7 is preferably 200 μm, more preferably 100 μm, and even more preferably 50 μm. By making the average thickness of the positive electrode substrate layer 7 equal to or greater than the lower limit, the strength of the positive electrode substrate layer 7 can be sufficiently increased, and the positive electrode layer 2 can be formed satisfactorily. By making the average thickness of the positive electrode substrate layer 7 equal to or less than the upper limit, the volume of the other components can be sufficiently secured.
[0156] (Positive electrode mixture layer) The positive electrode mixture layer 6 can be formed from a so-called positive electrode mixture containing a positive electrode active material. The positive electrode mixture may contain a positive electrode mixture or a positive electrode composite containing a positive electrode active material and a solid electrolyte. The sulfide solid electrolyte may be used as the solid electrolyte. The positive electrode mixture forming the positive electrode mixture layer 6, like the negative electrode mixture, may contain optional components such as a solid electrolyte, a conductive agent, a binder, and a filler, as necessary. The positive electrode mixture layer may be in a form that does not contain a solid electrolyte.
[0157] <Cathode active material> The positive electrode active material contained in the positive electrode mixture layer 6 can be a known material that is generally used in all-solid-state batteries. x M e O y (Me represents at least one transition metal) 2 Li with type crystal structure x Chief of Staff 2 , Li x NiO 2 , Li x MnO 3 , Li x Ni α Co (1-α) O 2 , Li x Ni α Mn β Co (1-α-β) O 2 Li with spinel crystal structure x Mn 2 O 4 , Li x Ni α Mn (2-α) O 4 etc.), Li w Me x (A.O. y ) z (Me represents at least one transition metal, and A represents, for example, P, Si, B, V, etc.) 4 , LiMnPO 4 , LiNiPO 4 , LiCoPO 4 , Li 3 V 2(PO 4 ) 3 , Li 2 MnSiO 4 , Li 2 CoPO 4 F, etc. The elements or polyanions in these compounds may be partially substituted with other elements or anion species. In the positive electrode active material layer, one of these compounds may be used alone, or two or more of them may be used in combination.
[0158] The positive electrode active material may be a lithium alloy such as Li-Al, Li-In, Li-Sn, Li-Pb, Li-Bi, Li-Ga, Li-Sr, Li-Si, Li-Zn, Li-Cd, Li-Ca, or Li-Ba, or a compound other than MnO represented by the above general formula. 2 , FeO 2 , TiO 2 , V 2 O 5 , V 6 O 13 , TiS 2 A material having an oxidation-reduction potential higher than that of the negative electrode material, such as
[0159] The lower limit of the content of the positive electrode active material in the positive electrode mixture is preferably 10% by mass, more preferably 15% by mass. The upper limit of the content of the positive electrode active material is preferably 60% by mass, more preferably 70% by mass, even more preferably 80% by mass, particularly preferably 90% by mass, and may be 95% by mass. By setting the content of the positive electrode active material within the above range, the electric capacity of the all-solid-state battery can be increased.
[0160] <Positive Electrode Mixture or Positive Electrode Composite> The positive electrode mixture is a mixture prepared by mixing the positive electrode active material and the solid electrolyte by mechanical milling, etc., in the same manner as in the case of the negative electrode. For example, the mixture of the positive electrode active material and the solid electrolyte can be obtained by mixing a particulate positive electrode active material and a particulate solid electrolyte. As in the case of the negative electrode, the positive electrode composite may be a composite having a chemical or physical bond between the positive electrode active material and the solid electrolyte, etc., or a composite obtained by mechanically combining the positive electrode active material and the solid electrolyte, etc. The composite is one in which the positive electrode active material and the solid electrolyte, etc. are present within one particle, and examples of the composite include one in which the positive electrode active material and the solid electrolyte, etc. form an aggregated state, and one in which a coating containing the solid electrolyte, etc. is formed on at least a part of the surface of the positive electrode active material. The positive electrode mixture or positive electrode composite may contain a solid electrolyte other than the sulfide solid electrolyte. The positive electrode active material, solid electrolyte, and the like contained in the positive electrode mixture constitute a positive electrode mixture or a positive electrode composite, which can improve ionic conductivity.
[0161] When the positive electrode mixture contains a solid electrolyte, the lower limit of the content of the solid electrolyte may be 5 mass%, and preferably 10 mass%. The upper limit of the content of the solid electrolyte in the positive electrode mixture is preferably 90 mass%, more preferably 85 mass%, further preferably 80 mass%, and particularly preferably 75 mass%. By setting the content of the solid electrolyte in the above range, the electric capacity of the all-solid-state battery can be increased.
[0162] The lower limit of the average thickness of the positive electrode mixture layer 6 is preferably 30 μm, more preferably 60 μm. The upper limit of the average thickness of the positive electrode mixture layer 6 is preferably 1000 μm, more preferably 500 μm, and even more preferably 200 μm. By making the average thickness of the positive electrode mixture layer 6 equal to or greater than the lower limit, an all-solid-state battery having a high energy density can be obtained. By making the average thickness of the positive electrode mixture layer 6 equal to or less than the upper limit, an all-solid-state battery having excellent high-rate discharge performance and a negative electrode with a high active material utilization rate can be obtained.
[0163] [Solid electrolyte layer] The solid electrolyte layer 3 contains an electrolyte for the solid electrolyte layer. In addition to the above-mentioned sulfide solid electrolyte, examples of the electrolyte for the solid electrolyte layer include oxide-based solid electrolytes, other sulfide solid electrolytes, dry polymer electrolytes, gel polymer electrolytes, and pseudo-solid electrolytes. Among these, the sulfide solid electrolyte is preferred from the viewpoints of good ion conductivity and easy interface formation, and the sulfide solid electrolyte is more preferred. By containing the sulfide solid electrolyte in the solid electrolyte layer 3, the solid electrolyte layer can exhibit high ion conductivity, and the internal resistance of the all-solid-state battery can be reduced.
[0164] The content of the sulfide solid electrolyte relative to the total amount of the solid electrolyte contained in the all-solid-state battery is preferably 50% by mass or more and 100% by mass or less, more preferably 70% by mass or more and 100% by mass or less, even more preferably 80% by mass or more and 100% by mass or less, and even more preferably 90% by mass or more and 100% by mass or less. In particular, it is preferable that the solid electrolyte contained in the all-solid-state battery is composed only of the sulfide solid electrolyte. In particular, since the sulfide solid electrolyte containing the element X has high thermal stability, by configuring the all-solid-state battery as described above, it is possible to fully enjoy the advantage of the all-solid-state battery, which can increase the upper limit of the operating temperature of the battery.
[0165] The electrolyte for the solid electrolyte layer may have a crystalline structure or may be amorphous without a crystalline structure. 3 PO 4 Oxides such as these, halogens, halogen compounds, etc. may also be added.
[0166] The average thickness of the solid electrolyte layer 3 is preferably 1 μm or more and 50 μm or less, and more preferably 3 μm or more and 20 μm or less. By setting the average thickness of the solid electrolyte layer 3 within the above range, it becomes possible to increase the energy density of the all-solid-state battery while reliably insulating the positive electrode and the negative electrode.
[0167] <Manufacturing method for all-solid-state batteries> The manufacturing method of the all-solid-state battery mainly includes, for example, a sulfide solid electrolyte preparation step, a negative electrode mixture preparation step, a solid electrolyte layer preparation step, a positive electrode mixture preparation step, and a lamination step of laminating the negative electrode layer, the solid electrolyte layer, and the positive electrode layer.
[0168] (Sulfide solid electrolyte production process) In this step, for example, a sulfide solid electrolyte is produced by the method for producing a sulfide solid electrolyte.
[0169] (Negative electrode mixture production process) In this step, a negative electrode mixture for forming a negative electrode layer is prepared. When the negative electrode mixture contains a mixture or composite containing a negative electrode active material and the sulfide solid electrolyte, this step includes mixing the negative electrode active material and the sulfide solid electrolyte by, for example, a mechanical milling method or the like to prepare a mixture or composite of the negative electrode active material and the sulfide solid electrolyte.
[0170] (Electrolyte production process for solid electrolyte layer) In this step, the above-mentioned electrolyte for the solid electrolyte layer is prepared to form the solid electrolyte layer. In this step, the electrolyte for the solid electrolyte layer can be obtained by processing a predetermined material for the electrolyte for the solid electrolyte layer by a mechanical milling method. The electrolyte for the solid electrolyte layer may be prepared by heating a predetermined material for the electrolyte for the solid electrolyte layer to a melting temperature or higher by a melting quenching method, melting and mixing the two at a predetermined ratio, and quenching. Other methods for synthesizing the electrolyte for the solid electrolyte layer include, for example, a solid-phase method in which the electrolyte is sealed under reduced pressure and fired, a liquid-phase method such as dissolution deposition, a gas-phase method (PLD), and firing in an argon atmosphere after mechanical milling. In addition, when the electrolyte for the solid electrolyte layer is the sulfide solid electrolyte, the above-mentioned sulfide solid electrolyte preparation step is performed in the preparation step of the electrolyte for the solid electrolyte layer.
[0171] (Positive electrode mixture production process) In this step, a positive electrode mixture for forming a positive electrode layer is prepared. The method for preparing the positive electrode mixture is not particularly limited and can be appropriately selected according to the purpose. For example, compression molding of the positive electrode active material, mechanical milling of a predetermined material of the positive electrode mixture, sputtering using a target material of the positive electrode active material, etc. can be mentioned. When the positive electrode mixture contains a mixture or composite containing the positive electrode active material and the sulfide solid electrolyte, this step includes, for example, mixing the positive electrode active material and the sulfide solid electrolyte using a mechanical milling method or the like to prepare a mixture or composite of the positive electrode active material and the sulfide solid electrolyte.
[0172] (Lamination process) In this process, an anode layer having an anode substrate layer and an anode mixture layer, a solid electrolyte layer, and a cathode layer having a cathode substrate layer and a cathode mixture layer are laminated. In this process, the anode layer, the solid electrolyte layer, and the cathode layer may be formed in sequence or in reverse, and the order of forming each layer is not particularly important. The anode layer is formed by pressure molding the anode substrate and the anode mixture, the solid electrolyte layer is formed by pressure molding an electrolyte for the solid electrolyte layer, and the cathode layer is formed by pressure molding the cathode substrate and the cathode mixture.
[0173] The negative electrode layer, the solid electrolyte layer, and the positive electrode layer may be laminated by pressure molding the negative electrode substrate, the negative electrode mixture, the electrolyte for the solid electrolyte layer, the positive electrode substrate, and the positive electrode mixture at the same time. The positive electrode layer, the negative electrode layer, or these layers may be molded in advance, and then pressure molded together with the solid electrolyte layer to laminate them.
[0174] <Other embodiments> The present invention is not limited to the above-described embodiment, and can be embodied in various other forms in addition to the above-described forms with various modifications and improvements.
[0175] In the above embodiment, the raw material compound containing only N, Li, and element M has been described as an example of the raw material compound containing N, element A, and element M, but the present invention is not limited thereto. For example, the raw material compound containing N, element A, and element M may further contain other elements as long as it does not interfere with solving the problems of the present invention.
[0176] The configuration of the all-solid-state battery according to the present invention is not particularly limited, and may include layers other than the negative electrode layer, the positive electrode layer, and the solid electrolyte layer, such as an intermediate layer or an adhesive layer. EXAMPLES
[0177] The present invention will be described in more detail below with reference to demonstration experiments, but the present invention is not limited to the following examples.
[0178] First, Example 1, Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 3 show the effect of the method for producing a sulfide solid electrolyte according to one embodiment of the present invention in suppressing the discharge of N to the outside of the system. [Example 1] The following process will result in 80(0.70Li 2 S 0.30P 2 S 5 )·20Li 3 / 2 Al 1 / 2 N was synthesized. (preparation process) Li 3 N and AlN were weighed out to a molar ratio of 1.2:1, mixed in a mortar, and pelletized. Then, the mixture was heat-treated at 750°C for 1 hour to obtain Li 3 / 2 Al 1 / 2 N was prepared. The Li 3 / 2 Al 1 / 2 N was determined by XRD measurement to be mainly composed of Li. 3 / 2 Al 1 / 2 It was confirmed that N. Next, Li was placed in an argon atmosphere glove box with a dew point of -50°C or less. 2 S (99.98%, Aldrich), P 2 S 5 (99%, Aldrich) and Li 3 / 2 Al1 / 2 The lithium, phosphorus, sulfur, nitrogen, and nitrogen were weighed out to give a molar ratio of 56:24:20, and then mixed in a mortar to prepare a composition containing lithium, phosphorus, sulfur, nitrogen, and aluminum. (Reaction process) The above composition was placed in a sealed 80 mL zirconia pot containing 160 g of zirconia balls with a diameter of 4 mm. The mixture was milled for 45 hours at a revolution speed of 510 rpm using a planetary ball mill (FRITSCH, model number Premium line P-7) to obtain an intermediate. (Heat treatment process) The intermediate was heat-treated for 2 hours to obtain a sulfide solid electrolyte. This heat treatment was performed at a temperature equal to or higher than the crystallization temperature, but not higher than 100°C above the crystallization temperature. The crystallization temperature was determined by measuring DSC. The DSC measurement was performed under the following conditions. That is, a DSC device (Rigaku Thermo Plus DSC8230) was used, and a SUS sealed pan was used, and the temperature was raised from room temperature to 400°C at a rate of 10°C / min. The composition prepared by the above synthesis procedure was designated as sample a, the intermediate was designated as sample b, and the sulfide solid electrolyte was designated as sample c.
[0179] [Example 2] The same procedure as in Example 1 was repeated except that the preparation process was changed as follows: 2 S 0.30P 2 S 5 )·20Li 3 / 2 B 1 / 2 N was synthesized. (preparation process) Li 3 N and BN were weighed out to a molar ratio of 1.1:1, mixed in a mortar, and pelletized. Then, the mixture was heat-treated at 800°C for 10 minutes to obtain Li 3 / 2 B 1 / 2 N was prepared. The Li 3 / 2 B 1 / 2 N was determined by XRD measurement to be mainly composed of Li. 3 / 2 B 1 / 2 It was confirmed that N. Next, Li was placed in an argon atmosphere glove box with a dew point of -50°C or less. 2 S (99.98%, Aldrich), P2 S 5 (99%, Aldrich) and Li 3 / 2 B 1 / 2 The lithium, phosphorus, sulfur, nitrogen, and nitrogen were weighed out to give a molar ratio of 56:24:20, and then mixed in a mortar to prepare a composition containing lithium, phosphorus, sulfur, nitrogen, and boron.
[0180] [Comparative Example 1] 56.8Li was prepared in the same manner as in Example 1, except that the preparation process was changed as follows: 2 S·27.0P 2 S 5 16.2Li 3 N was synthesized. (preparation process) Li was placed in an argon atmosphere glove box with a dew point of -50°C or less. 2 S (99.98%, Aldrich), P 2 S 5 (99%, Aldrich), and Li 3 The lithium, phosphorus, sulfur, and nitrogen were weighed out to give a molar ratio of 56.8:27.0:16.2, and then mixed in a mortar to prepare a composition containing lithium, phosphorus, sulfur, and nitrogen.
[0181] [Comparative Example 2] The same procedure as in Example 1 was repeated except that the preparation process was changed as follows: 2 S 0.30P 2 S 5 )·20Li 3 / 2 Al 1 / 2 N was synthesized. (preparation process) Li was placed in an argon atmosphere glove box with a dew point of -50°C or less. 2 S (99.98%, Aldrich), P 2 S 5 (99%, Aldrich), Li 3 N and AlN were weighed out to have a molar ratio of 56:24:10:10, and then mixed in a mortar to prepare a composition containing Li, P, S, N, and Al.
[0182] [Comparative Example 3] The same procedure as in Example 1 was repeated except that the preparation process was changed as follows: 2 S 0.30P 2 S 5 )·20Li 7 / 4 V 1 / 4 N was synthesized. (preparation process) Li 3 N and VN were weighed out in a molar ratio of 3:1, mixed in a mortar, and pelletized. Then, the mixture was heat-treated at 750°C for 10 hours to obtain Li 7 / 4 V 1 / 4 N was prepared. The Li 7 / 4 V 1 / 4 N was determined by XRD measurement to be mainly composed of Li. 7 / 4 V 1 / 4 It was confirmed that N. Next, Li was placed in an argon atmosphere glove box with a dew point of -50°C or less. 2 S (99.98%, Aldrich), P 2 S 5 (99%, Aldrich) and Li 7 / 4 V 1 / 4 The lithium, phosphorus, sulfur, nitrogen, and vanadium were weighed out to give a molar ratio of 56:24:20, and then mixed in a mortar to prepare a composition containing lithium, phosphorus, sulfur, nitrogen, and vanadium.
[0183] [evaluation] (1) XRD X-ray diffraction measurements were performed by the following method. Using an airtight sample holder for X-ray diffraction measurements, the sulfide solid electrolyte powders of the examples and comparative examples were filled in an argon atmosphere with a dew point of -50°C or less. Powder X-ray diffraction measurements were performed using an X-ray diffractometer (Rigaku's "miniFlex II"). The radiation source was CuKα radiation, the tube voltage was 30 kV, the tube current was 15 mA, and the diffracted X-rays were passed through a 30 μm thick Kβ filter and detected by a high-speed one-dimensional detector (model number: D / teX Ultra2). The sampling width was 0.01°, the scan speed was 5° / min, the divergence slit width was 0.625°, the receiving slit width was 13 mm (OPEN), and the scattering slit width was 8 mm.
[0184] (2) Ionic conductivity (σ) Ionic conductivity (σ25 The activation energy (E) was calculated by measuring the ionic conductivity at 25°C using Bio-Logic's VMP-300 and the AC impedance as described above. For some of the examples and comparative examples, the ionic conductivity was also measured at temperatures of -30°C, -20°C, -10°C, 0°C, and 50°C, and the activation energy (E) was calculated by the Arrhenius equation. a ) was calculated.
[0185] Table 4 shows the XRD patterns and the ionic conductivity (σ 25 ) is shown. As shown in Table 4, the sulfide solid electrolytes of all the examples and comparative examples were confirmed to have a specific crystal structure A, with peaks observed in the XRD spectrum. The specific crystal structure A is a crystal structure having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, 29.8°±0.5°, and 30.9°±0.5° in X-ray diffraction measurement. It was also confirmed that the sulfide solid electrolytes of Example 1, Example 2, and Comparative Example 3 exhibited the same level of ionic conductivity. Therefore, it can be said that Example 1, Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 3 have similar structures.
[0186] [Table 4]
[0187] For each sample of Example 1, Example 2, Comparative Example 1, and Comparative Example 2, the contents of Li, B, Al, and P in the sample were determined using an ICP optical emission spectrometer. For each sample of Example 1, Example 2, and Comparative Examples 1 to 3, the contents of N in the sample were determined using an oxygen / nitrogen / hydrogen analyzer. From the analysis results, the rate of change in the N content in the sample was calculated. The analysis results are shown in Table 5. In the table, "no change" indicates that the rate of change in the N content relative to sample a was ±5 mass% or less.
[0188] [Table 5]
[0189] From Table 5, it can be seen that the N content ratios in Sample a, Sample b, and Sample c hardly change in Examples 1 and 2. In other words, in Examples 1 and 2, the N content hardly changes even through each of the reaction process and heat treatment process, and it can be seen that the emission of N to the outside of the system was suppressed. On the other hand, in Comparative Examples 1, 2, and 3, it is found that the N content in Sample a, Sample b, and Sample c decreases in the order of Sample a, Sample b, and Sample c. In other words, it is found that in Comparative Examples 1, 2, and 3, the N content decreases with each step of the reaction step and heat treatment step, and N is discharged outside the system. From the above, it was demonstrated that Al and B, which were selected based on the prediction of their N emission suppression effect using first-principles calculations, actually have an effect. Furthermore, it was also demonstrated that V, which was predicted to have no effect in suppressing N emissions using first-principles calculations, actually does not have an effect.
[0190] Next, Examples 3 to 20 and Comparative Examples 4 to 8 show the effect of improving the thermal stability of the sulfide solid electrolyte according to one embodiment of the present invention. [Example 3] The following treatment yielded the compound with the formula 85(0.80(0.70Li 2 S 0.30P 2 S 5 )·0.20Li 3 / 2 Al 1 / 2 We synthesized a sulfide solid electrolyte represented by the formula (N) 10LiBr 5LiI. Li 3 N and AlN were weighed out to a molar ratio of 1.2:1, mixed in a mortar, and pelletized. Then, the mixture was heat-treated at 750°C for 1 hour to obtain Li 3 / 2 Al 1 / 2 N was prepared. The Li 3 / 2 Al 1 / 2 N was determined by XRD measurement to be mainly composed of Li. 3 / 2 Al 1 / 2 It was confirmed that N. Next, Li was placed in an argon atmosphere glove box with a dew point of -50°C or less. 2 S (99.98%, Aldrich), P 2 S 5 (99%, Aldrich), LiBr(99.999%, Aldrich), LiI(99.999%, Aldrich), and Li 3 / 2 Al 1 / 2 N was weighed out so that the molar ratio was 47.6:20.4:10:5:17, and then mixed in a mortar. This mixed sample was placed in a sealed 80 mL zirconia pot containing 160 g of zirconia balls with a diameter of 4 mm. Milling was performed for 45 hours at a revolution speed of 510 rpm using a planetary ball mill (FRITSCH, model number Premium line P-7). Heat treatment was performed for 2 hours at 245 ° C to obtain a sulfide solid electrolyte of Example 3. This heat treatment temperature was set to be equal to or higher than the crystallization temperature, but not higher than 100 ° C above the crystallization temperature. The crystallization temperature was determined by taking out a part of the sample after the milling treatment and subjecting it to DSC measurement. The DSC measurement was performed under the following conditions. That is, a DSC device (Rigaku, Thermo Plus DSC8230) was used, and a SUS sealed pan was used, and the temperature was raised from room temperature to 400 ° C at 10 ° C / min.
[0191] [Comparative Example 4 and Comparative Example 5] The composition of the sulfide solid electrolyte is 85(0.75Li 2 S 0.25P 2 S 5 )·10LiBr·5LiI, 85(0.72Li 2 S 0.25P 2 S 5 0.020Li 3 The sulfide solid electrolytes of Comparative Example 4 and Comparative Example 5 were synthesized in the same manner as in Example 3, except that the catalyst composition was changed to (N)·10LiBr·5LiI and the heat treatment temperature was 225° C. in both cases.
[0192] [Examples 4 to 7, Comparative Example 6] The composition of the sulfide solid electrolyte is 80(0.80(0.70Li 2 S 0.30P 2 S 5)·0.20Li 3 / 2 Al 1 / 2 N)·12LiBr·8LiI, 80(0.70(0.67Li 2 S 0.33P 2 S 5 )·0.30Li 3 / 2 Al 1 / 2 N)·12LiBr·8LiI, 80(0.80(0.70Li 2 S 0.30P 2 S 5 )·0.20Li 3 / 2 B 1 / 2 N)·12LiBr·8LiI, 80(0.80(0.70Li 2 S 0.30P 2 S 5 )·0.20Li 5 / 3 S 1 / 3 N)·12LiBr·8LiI, 80(0.6975Li 2 S 0.25P 2 S 5 0.035Li 3 The sulfide solid electrolytes of Examples 4 to 7 and Comparative Example 6 were synthesized in the same manner as in Example 3, except that the catalyst used was changed to (N)·12LiBr·8LiI and the heat treatment temperatures were changed to 255° C., 275° C., 270° C., 270° C., and 250° C., respectively. In addition to the sample with the heat treatment temperature of 255°C, the sulfide solid electrolyte of Example 4 also synthesized samples with the heat treatment temperatures of 215°C, 230°C, 275°C, 290°C, and 310°C. In addition to the sample with the heat treatment temperature of 275°C, the sulfide solid electrolyte of Example 5 also synthesized samples with the heat treatment temperatures of 235°C, 290°C, 310°C, and 330°C. In addition to the sample with the heat treatment temperature of 270°C, the sulfide solid electrolyte of Example 6 also synthesized samples with the heat treatment temperatures of 230°C, 270°C, 290°C, 310°C, and 330°C. In addition to the sample with the heat treatment temperature of 270°C, the sulfide solid electrolyte of Example 7 also synthesized samples with the heat treatment temperatures of 230°C, 290°C, 310°C, and 330°C. In addition to the sulfide solid electrolyte of Comparative Example 6 in which the heat treatment temperature was 250°C, samples in which the heat treatment temperatures were 210°C and 230°C were also synthesized. The sulfide solid electrolytes synthesized at each heat treatment temperature are named, in order from lowest to highest heat treatment temperature, as Examples 4-1 to 4-6, 5-1 to 5-5, 6-1 to 6-5, 7-1 to 7-5, and Comparative Examples 6-1 to 6-3, respectively.
[0193] [Example 8, Comparative Example 7] The composition of the sulfide solid electrolyte was 75(0.80(0.70Li 2 S 0.30P 2 S 5 )·0.20Li 3 / 2 Al 1 / 2 N) 15LiBr 10LiI, 75 (0.72Li 2 S 0.25P 2 S 5 0.020Li 3 The sulfide solid electrolytes of Example 8 and Comparative Example 7 were synthesized in the same manner as in Example 1, except that the mixture was changed to (N)·15LiBr·10LiI and the heat treatment temperatures were 215° C. and 195° C., respectively.
[0194] [Examples 9 to 11, Comparative Example 8] The composition of the sulfide solid electrolyte is 90(0.80(0.70Li 2 S 0.30P 2 S 5 )·0.20Li 3 / 2 Al 1 / 2 N)·10LiBr, 80(0.80(0.70Li 2 S 0.30P 2 S 5 )·0.20Li 3 / 2 Al 1 / 2 N)·20LiBr, 70(0.80(0.70Li 2 S 0.30P 2 S 5 )·0.20Li 3 / 2 Al 1 / 2 N) 30LiBr, 90(0.72Li 2 S 0.25P 2 S 5 0.020Li 3The sulfide solid electrolytes of Examples 9, 10, and 11 and Comparative Example 8 were synthesized in the same manner as in Example 3, except that the catalyst used was changed to (N)·10LiBr and the heat treatment temperatures were changed to 265° C., 250° C., 240° C., and 225° C., respectively.
[0195] [Examples 12 and 13] The composition of the sulfide solid electrolyte is 90(0.80(0.70Li 2 S 0.30P 2 S 5 )·0.20Li 3 / 2 Al 1 / 2 N)·10LiI, 80(0.80(0.7Li 2 S 0.30P 2 S 5 )·0.20Li 3 / 2 Al 1 / 2 The sulfide solid electrolytes of Examples 12 and 13 were synthesized in the same manner as in Example 3, except that the catalyst was changed to (N)·20LiI and the heat treatment temperatures were changed to 255° C. and 240° C., respectively.
[0196] [Examples 14 to 17] The composition of the sulfide solid electrolyte was 80(0.97(0.745Li 2 S 0.255P 2 S 5 )·0.03Li 3 / 2 B 1 / 2 N)·12LiBr·8LiI, 80(0.95(0.74Li 2 S 0.26P 2 S 5 )·0.05Li 3 / 2 B 1 / 2 N)·12LiBr·8LiI, 80(0.90(0.73Li 2 S 0.27P 2 S 5 )·0.10Li 3 / 2 B 1 / 2 N)·12LiBr·8LiI, 80(0.85(0.715Li 2 S 0.285P 2 S 5 )·0.15Li 3 / 2 B 1 / 2The sulfide solid electrolytes of Examples 14 to 17 were synthesized in the same manner as in Example 3, except that the catalyst composition was changed to (N)·12LiBr·8LiI and the heat treatment temperature was changed to 250° C.
[0197] [Examples 18 to 20] The composition of the sulfide solid electrolyte was 75(0.80(0.70Li 2 S 0.30P 2 S 5 )·0.20Li 3 / 2 B 1 / 2 N)·15LiBr·10LiI, 70(0.80(0.70Li 2 S 0.30P 2 S 5 )·0.20Li 3 / 2 B 1 / 2 N)·17LiBr·13LiI, 65(0.80(0.70Li 2 S 0.30P 2 S 5 )·0.20Li 3 / 2 B 1 / 2 The sulfide solid electrolytes of Examples 18 to 20 were synthesized in the same manner as in Example 3, except that the catalyst used was changed to (N)·20LiBr·15LiI and the heat treatment temperatures were changed to 230° C., 195° C., and 185° C., respectively.
[0198] The sulfide solid electrolytes of Examples 3 to 20 are represented by the general formula (100-z 1 -z 2 ){(1-y)[xLi 2 S (1-x)P 2 S 5 ]·yLi α M β N}·z 1 LiX 1 z 2 LiX 2 The sulfide solid electrolytes of Comparative Examples 5 to 7 are represented by the general formula (100-z 1 -z 2 ){(x-1.5y)Li 2 S (1-x)P 2 S 5 ·yLi 3 N}·z 1 LiX 1 z2 LiX 2 It is expressed as:
[0199] Tables 6 to 12 show the crystal structures identified from the XRD patterns of Examples 3 to 20 and Comparative Examples 4 to 8. Table 13 shows the crystal structures identified from the XRD patterns of Examples 4-1 to 4-6, Examples 5-1 to 5-5, Examples 6-1 to 6-5, Examples 7-1 to 7-5, and Comparative Examples 6-1 to 6-3. In the table, "HICP" represents a crystal phase having diffraction peaks at 2θ=20.2°±0.5° and 23.6°±0.5° in X-ray diffraction measurement using CuKα radiation. "LICP" represents a crystal phase having diffraction peaks at 2θ=21.0°±0.5° and 28.0°±0.5° in X-ray diffraction measurement using CuKα radiation. "Specific crystal structure C" represents a crystal phase having diffraction peaks at 2θ=17.5°±0.5° and 24.9°±0.5° in X-ray diffraction measurement using CuKα radiation. "β-Li 3 P.S. 4 " indicates a crystalline phase having diffraction peaks at 2θ=17.5°±0.5°, 18.1°±0.5°, 29.1°±0.5°, 29.9°±0.5°, and 31.2°±0.5° in X-ray diffraction measurement using CuKα radiation. "Unknown" indicates a peak whose crystal phase attribution is unknown. 3 shows the XRD patterns of Examples 4-1 to 4-6, and FIG 4 shows the XRD patterns of Comparative Examples 6-1 to 6-3.
[0200] Tables 6 to 12 show the ionic conductivities (σ 25 ) and activation energy (E a Table 13 shows the ionic conductivities (σ) at 25° C. of Examples 4-1 to 4-6, Examples 5-1 to 5-5, Examples 6-1 to 6-5, Examples 7-1 to 7-5, and Comparative Examples 6-1 to 6-3. 25 ) and activation energy (E a ) is shown.
[0201] (3) DSC DSC measurements were carried out as follows: A DSC device (Rigaku Thermo Plus DSC8230) was used, and a SUS sealed pan was used, and the temperature was raised from room temperature to 400° C. at a rate of 10° C. / min.
[0202] The intermediates after milling and before heat treatment were subjected to DSC measurement for the sulfide solid electrolytes of Examples 4 to 7, Examples 14 to 17, and Comparative Example 6. DSC curves of these samples are shown in Figs. 5 and 6.
[0203] [Table 6]
[0204] [Table 7]
[0205] [Table 8]
[0206] [Table 9]
[0207] [Table 10]
[0208] [Table 11]
[0209] [Table 12]
[0210] [Table 13]
[0211] From Table 6, it can be seen that in the sulfide solid electrolytes of Comparative Example 4 and Comparative Example 5, LICPs are generated when the heat treatment temperature is set to 225° C., and the ionic conductivity at 25° C. is reduced. On the other hand, it can be seen that the sulfide solid electrolyte of Example 3 containing Li, P, S, N, Br, I, and Al does not generate LICPs and exhibits high ionic conductivity, even though it is heat-treated at a higher temperature than the sulfide solid electrolytes of Comparative Example 4 and Comparative Example 5. In other words, it can be seen that in the sulfide solid electrolyte of Example 3, the lower limit of the heat treatment temperature at which the ionic conductivity decreases is higher than that of the sulfide solid electrolytes of Comparative Example 4 and Comparative Example 5.
[0212] From Table 7, it can be seen that the sulfide solid electrolytes of Examples 4 to 7 did not generate LICPs and exhibited high ionic conductivity, despite being heat-treated at a higher temperature than the sulfide solid electrolyte of Comparative Example 6. In other words, it can be seen that the lower limit of the heat treatment temperature at which the ionic conductivity decreases is higher in the sulfide solid electrolytes of Examples 4 to 7 than in the sulfide solid electrolyte of Comparative Example 6.
[0213] From Table 8, it can be seen that the sulfide solid electrolyte of Example 8 exhibits higher ionic conductivity despite being heat-treated at a higher temperature than the sulfide solid electrolyte of Comparative Example 7. In other words, it can be seen that the lower limit of the heat treatment temperature at which the ionic conductivity decreases is higher in the sulfide solid electrolyte of Example 8 than in the sulfide solid electrolyte of Comparative Example 7. This is believed to be because the phase transition from HICP to LICP is suppressed in the sulfide solid electrolyte of Example 8.
[0214] From Table 9, it can be seen that the sulfide solid electrolytes of Examples 9 to 11 all exhibit higher ion conductivity than the sulfide solid electrolyte of Comparative Example 8, despite being heat-treated at a higher temperature. Also, it can be seen that even when the sulfide solid electrolyte contains only Br as the element X, the effect of the present invention of improving the thermal stability of the high Li ion conductive phase of the sulfide solid electrolyte can be obtained. Furthermore, comparing Example 9 and Comparative Example 8, which have the same Br content, it can be seen that neither HICPs nor LICPs were produced in Comparative Example 8, whereas HICPs were produced in Example 9. In other words, when the sulfide solid electrolyte contains Li, P, S, N, element X, and element M, it was found that an effect of being able to produce HICPs with a smaller content of element X was observed compared to when element M was not contained.
[0215] From Table 10, it can be seen that even when the sulfide solid electrolyte contains only I as the element X, a sulfide solid electrolyte containing HICP can be obtained.
[0216] From Table 11, it can be seen that the sulfide solid electrolytes of Examples 6 and 15 to 17 exhibited the presence of HICPs and high ionic conductivity, despite being heat-treated at a temperature higher than that of the sulfide solid electrolyte of Comparative Example 6. In other words, it can be seen that the sulfide solid electrolytes of these Examples have a higher lower limit of the heat treatment temperature at which the ionic conductivity decreases than that of the sulfide solid electrolyte of Comparative Example 6. 6, the sulfide solid electrolytes of Examples 6 and 14 to 17 have a crystallization peak presumably derived from HICP and a β-Li 3 P.S. 4 For example, in Comparative Example 6, the crystallization peak suspected to be due to HICP and the crystallization peak due to β-Li 3 P.S. 4 The crystallization peaks derived from the Li-ion conductive phase were observed near 190° C. and 260° C. in Example 13, whereas in Example 14, they were observed near 190° C. and 280° C. in Example 15. This shows that the temperature range in which HICPs exist stably is expanded and the thermal stability of the high Li-ion conductive phase is improved in the sulfide solid electrolyte of the example. In addition, the crystallization peaks inferred to be due to HICP in Fig. 6 are peaks observed in the range of approximately 180°C to 220°C. 3 P.S. 4The crystallization peaks derived from the above-mentioned crystallization methods refer to peaks observed around 345°C, 280°C, 300°C, 310°C, 335°C, and 260°C in Example 6, Examples 14 to 16, and Comparative Example 6, respectively. From the above, it can be seen that even when the content ratio N / P of N to P of the sulfide solid electrolyte is 0.060, 0.10, 0.21, 0.31, or 0.42, the effect of improving the thermal stability of the high Li-ion conductive phase can be obtained.
[0217] From Table 12, it can be seen that even when the content ratio X / P of the element X to P in the sulfide solid electrolyte is 0.52, 0.70, 0.90, or 1.12, a sulfide solid electrolyte containing HICP can be obtained.
[0218] From Comparative Examples 6-1 to 6-3 shown in Table 13, it can be seen that in the sulfide solid electrolyte of Comparative Example 6, when the heat treatment temperature is 250° C. or higher, HICP is converted into LICP and β-Li 3 P.S. 4 It can also be seen that the ionic conductivity at 25°C decreases significantly in accordance with this phase transition. On the other hand, it is understood from Examples 4-1 to 4-6 that in the sulfide solid electrolyte of Example 4, HICP exists and high ionic conductivity can be maintained even when the heat treatment temperature is increased to 290°C. Moreover, it is understood from Examples 5-1 to 5-5 that the sulfide solid electrolyte of Example 5 also has HICPs over a wide temperature range and can maintain high ionic conductivity. Furthermore, from Examples 6-1 to 6-5 and Examples 7-1 to 7-5, it can be seen that even when B and Si are contained instead of Al as element M, the effect of the present invention of maintaining high ionic conductivity over a wide temperature range can be obtained. That is, it can be seen from Table 13 that the sulfide solid electrolytes of Examples 4 to 7 have a wider heat treatment temperature range in which the ionic conductivity does not decrease. In addition, from the comparison of Examples 6 and 7 with Examples 4 and 5 in Table 13, when the sulfide solid electrolyte contains either Si or B as the element M, the heat treatment temperature range in which the ion conductivity does not decrease is at least 80 ° C., and it can be seen that the thermal stability of the high Li ion conductive phase is particularly excellent. The peaks near 210 ° C. in the DSC curves of Examples 6 and 7 in FIG. 5 are crystallization peaks that are presumed to be derived from HICP. Therefore, it can be presumed that in Examples 6 and 7, the heat treatment temperature range in which the ion conductivity does not decrease is 100 ° C. The reason why such results were obtained is unclear, but it is considered that, for example, the strength of the bond energy between either Si or B and N was a value suitable for exerting the effects of the present invention.
[0219] As is clear from Tables 6 to 13, it was confirmed that the lower limit of the heat treatment temperature at which the ionic conductivity decreases is increased and the heat treatment temperature range at which the ionic conductivity does not decrease is expanded in the sulfide solid electrolytes of the examples. In other words, the sulfide solid electrolytes containing Li, P, S, N, element X, and element M were excellent in thermal stability of HICP. This is thought to be because the emission of N to the outside of the system during the production process was suppressed, and the thermal stability improving effect due to the sulfide solid electrolyte containing N was fully exerted.
[0220] The method for producing a sulfide solid electrolyte according to one embodiment of the present invention can suppress the emission of N to the outside of the system, and can also suppress the emission of Li 2 It has been suggested that the precipitation of S can be suppressed. 2 If the precipitation of S can be suppressed, the atmospheric stability of the sulfide solid electrolyte can be improved, which is preferable.
[0221] That is, from Examples 21 to 41, Comparative Example 9, and Comparative Example 10, the method for producing a sulfide solid electrolyte according to one embodiment of the present invention can be understood as follows: 2 This suggests that the precipitation of S can be suppressed.
[0222] [Example 21] By the following treatment, the composition formula (100-z)(yLi 2S·(1-y)P 2 S 5 )·zLi α M β Li in N α M β N is Li 3 / 2 Al 1 / 2 N, z = 1, y = 0.70, i.e., 99(0.7Li 2 S 0.3P 2 S 5 )·1Li 3 / 2 Al 1 / 2 N was synthesized. Li 3 N and AlN were weighed out to a molar ratio of 1.2:1, mixed in a mortar, and pelletized. Then, the mixture was heat-treated at 750°C for 1 hour to obtain Li 3 / 2 Al 1 / 2 N was produced. Next, Li was placed in an argon atmosphere glove box with a dew point of -50°C or less. 2 S (99.98%, Aldrich), P 2 S 5 (99%, Aldrich) and Li 3 / 2 Al 1 / 2 N was weighed out so that the molar ratio was 69.3:29.7:1.0, and then mixed in a mortar. This mixed sample was placed in a sealed 80 mL zirconia pot containing 160 g of zirconia balls with a diameter of 4 mm. A milling process was performed for 45 hours at a revolution speed of 510 rpm using a planetary ball mill (FRITSCH, model number Premium line P-7). Heat treatment was performed for 2 hours to obtain the sulfide solid electrolyte of Example 1. This heat treatment was performed at a temperature equal to or higher than the crystallization temperature and equal to or lower than the crystallization temperature plus 100°C. The crystallization temperature was determined by measuring DSC. The DSC measurement was performed under the following conditions. That is, a DSC device (Rigaku, Thermo Plus DSC8230) was used, and a SUS sealed pan was used, and the temperature was raised from room temperature to 400°C at a rate of 10°C / min.
[0223] [Examples 22 to 29] The composition formula of sulfide solid electrolyte is (100-z)(yLi 2 S·(1-y)P 2 S5 )·zLi α M β The sulfide solid electrolytes of Examples 22 to 29 were synthesized in the same manner as in Example 21, except that the value of z in N was changed to 5, 7, 10, 15, 20, 25, 30, or 40.
[0224] [Examples 30 to 32] The composition formula of sulfide solid electrolyte is (100-z)(yLi 2 S·(1-y)P 2 S 5 )·zLi α M β The sulfide solid electrolytes of Examples 30 to 32 were synthesized in the same manner as in Example 21, except that in N, y=0.67 and the value of z was changed to 20, 25, and 30, respectively.
[0225] [Examples 33 to 36] Li 3 N and BN were weighed out so that the molar ratio was 1.1:1, mixed in a mortar, pelletized, and then heat-treated at 800°C for 10 minutes to obtain Li 3 / 2 B 1 / 2 N was prepared. The Li 3 / 2 B 1 / 2 For N, XRD measurements showed that the main phase was Li 3 / 2 B 1 / 2 It was confirmed that N. The composition formula of sulfide solid electrolyte is (100-z)(yLi 2 S·(1-y)P 2 S 5 )·zLi α M β Li in N α M β N to Li 3 / 2 B 1 / 2 The sulfide solid electrolytes of Examples 33 to 36 were synthesized in the same manner as in Example 21, except that N was changed to N and the value of z was changed to 1, 10, 20, or 30.
[0226] [Examples 37 to 41] Li 3 N and Si 3 N 4were weighed out to a molar ratio of 5.1:1, mixed in a mortar, pelletized, and heat-treated at 800°C for 10 minutes to obtain Li 5 / 3 S 1 / 3 N was produced. The Li 5 / 3 S 1 / 3 Regarding N, XRD measurement revealed that the main phase is Li5 / 3Si 1 / 3 It was confirmed that N. The composition formula of sulfide solid electrolyte is (100-z)(yLi 2 S·(1-y)P 2 S 5 )·zLi α M β Li in N α M β N to Li 5 / 3 S 1 / 3 The sulfide solid electrolytes of Examples 37 to 41 were synthesized in the same manner as in Example 21, except that N was changed to N and the value of z was changed to 1.5, 15, 20, 30, and 45.
[0227] [Comparative Example 9] The composition formula of sulfide solid electrolyte is (100-z)(yLi 2 S·(1-y)P 2 S 5 )·zLi α M β Li in N α M β N to Li 3 A sulfide solid electrolyte of Comparative Example 9 was synthesized in the same manner as in Example 21, except that the value of N was changed to N and the value of z was changed to 20.
[0228] [Comparative Example 10] The composition formula of sulfide solid electrolyte is (100-z)(yLi 2 S·(1-y)P 2 S 5 )·zLi α M β A sulfide solid electrolyte of Comparative Example 10 was synthesized in the same manner as in Comparative Example 9, except that in N, y=0.68 and the value of z was changed to 16.
[0229] [evaluation] (1) XRD, ionic conductivity (σ) X-ray diffraction measurements were performed using the method described above. The ionic conductivity (σ 25 ) was determined by measuring AC impedance using Bio-Logic's VMP-300 according to the method described above.
[0230] (2) Raman spectroscopy The Raman spectrum was measured by the following method. A laser Raman spectrophotometer (Horiba, Ltd., "LabRAM HR Revolution") was used, and the excitation laser wavelength was 532 nm (YAG laser), the grating was 600 gr / mm, and the 100 cm -1 From 1800cm -1 Raman spectroscopy was performed in the wavenumber range of
[0231] Table 14 shows the ionic conductivity at 25°C, the crystal structure identified from the XRD pattern, and the Raman spectrum of Examples 21 to 41, Comparative Example 9, and Comparative Example 10. In the table, "specific crystal structure A" represents a crystal phase having diffraction peaks at 2θ=2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, 29.8°±0.5°, and 30.9°±0.5° in X-ray diffraction measurement using CuKα radiation. "Specific crystal structure B" represents a crystal phase having diffraction peaks at 2θ=2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, and 29.8°±0.5° in X-ray diffraction measurement using CuKα radiation. "-" indicates that the measurement was not performed.
[0232] [Table 14]
[0233] In the sulfide solid electrolyte of Comparative Example 9, Li 2 Only the peaks due to the crystal structure of Li 3 When N is used, Li 2 It is clear that S is easily precipitated. The reason for this result is unclear, but Li 3The dramatic reaction of N with other raw materials produces Li 2 This is thought to be due to the precipitation of S.
[0234] In Examples 21 to 35 and Examples 37 to 40, Li 2 Among them, a comparison with the examples (Examples 26, 35, 39, and Comparative Example 9) in which z=20 and y=0.70 shows that the sulfide solid electrolyte of the examples has Li 2 It was confirmed that the precipitation of S was suppressed.
[0235] In addition, the sulfide solid electrolytes of Examples 27 to 29, 32, 39, and 40 all had a higher Li / P content relative to P than the sulfide solid electrolyte of Comparative Example 10. 2 In particular, in Example 29, the Li content ratio to P was 4.00, which was higher than those of Comparative Examples 9 and 10. 2 The sulfide solid electrolytes of Examples 26 and 35 had almost the same Li / P ratio as the sulfide solid electrolyte of Comparative Example 10, but the peak of Li 2 No S peak was observed. The sulfide solid electrolyte of Example 32 has a value of y that is almost the same as that of Comparative Example 10, and the Li / P ratio is also the same. 2 No S peak was observed. In sulfide solid electrolytes, when the Li content is high, Li 2 Since the above results were obtained, it is believed that the sulfide solid electrolyte manufacturing method of the embodiment has a tendency to precipitate Li. 2 It was suggested that the precipitation of S was suppressed.
[0236] That is, from the comparison of Examples 28, 29, 36, 40 and 41, when the element M contains Al, Li 2 This suggests that the inhibition of S precipitation is significant.
[0237] From the above, in the method for producing the sulfide solid electrolyte of the embodiment, Li 2 It was suggested that the precipitation of S was suppressed. The sulfide solid electrolyte contains the element M, which 2 The reason why the precipitation of S can be suppressed is thought to be as follows. 3 When N is used, Li 3 N and P 2 S 5 and reacted dramatically to N 2 is released, and Li 2 S precipitates. This is because Li 3 This is believed to be because the defect formation energy of N is small. α M β The defect formation energy of N is Li 3 Since the defect formation energy of N is larger than that of N, the reaction proceeds slowly during the synthesis of sulfide-based solid electrolytes, and N 2 and Li 2 The precipitation of S is suppressed.
[0238] Although the present invention has been described in detail above, the above-mentioned embodiments are merely examples, and the invention disclosed herein includes various modifications and alterations of the above-mentioned specific examples. [Industrial Applicability]
[0239] An all-solid-state battery including a sulfide solid electrolyte according to the present invention can be suitably used, for example, as a lithium-ion all-solid-state battery for HEVs. [Explanation of symbols]
[0240] 1. Negative electrode layer 2 Positive electrode layer 3 Solid electrolyte layer 4 Negative electrode base material layer 5. Negative electrode mixture layer 6 Positive electrode mixture layer 7 Positive electrode substrate layer 10 All-solid-state battery
Claims
[Claim 1] A sulfide solid electrolyte having a crystal structure containing P, S, N, element A, element X, and element M as constituent elements, where A represents at least one element selected from the group consisting of Li, Na, and K. X represents at least one element selected from the group consisting of Cl, Br, and I. M represents at least one element selected from the group consisting of Al, Ta, Si, Sc, Mg, Nb, B, Hf, C, P, Zr, and Ti.
Citation Information
Patent Citations
Method of producing sulfide solid electrolyte material
JP2015011898A
Sulfide solid electrolyte, lithium solid battery and method for manufacturing sulfide solid electrolyte
JP2018041671A
Sulfide solid electrolyte and method for producing the same
JP2018156735A